Vapor deposition apparatus and technology for using high-purity polymer-derived silicon carbide
By using polymer-derived ceramic SiC compositions and vapor deposition technology, the problem of preparing high-purity silicon carbide materials has been solved, enabling the preparation of low-cost, high-purity silicon carbide materials that meet the performance requirements of semiconductors and other demanding applications.
Patent Information
- Application Number
- CN202111220327.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2015-09-24
- Filing Date
- 2016-09-23
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2036-09-23
AI Technical Summary
Existing technologies cannot effectively provide high-purity silicon carbide materials, especially high-purity single-crystal carbide materials for semiconductors and other finished products. Furthermore, existing methods are costly and cannot achieve a purity of over 99.9%, thus failing to meet commercial demands.
By using polymer-derived ceramic SiC compositions and controlling the impurity content to less than about 50 ppm, high-purity silicon carbide materials are prepared using vapor deposition technology. These materials include SiC4 structural configurations and specific band gaps, thermal conductivity, Young's modulus, and other properties, providing high-purity SiC wafers and SiC pear-shaped crystals.
This technology enables the low-cost preparation of high-purity silicon carbide materials, meeting the purity requirements of semiconductors and other demanding applications. It also improves the thermal conductivity, Young's modulus, and oxidation resistance of the materials, reduces microtube density, and enhances the reliability and efficiency of the materials.
Smart Images

Figure CN114000197B_ABST
Abstract
Description
[0001] Divisional Application Instructions
[0002] This application is a divisional application of an invention patent application filed on September 23, 2016, with application number 201680067713.7 and invention name “Vapor deposition device and technology using high-purity polymer-derived silicon carbide”. Technical Field
[0003] The present invention relates to improvements in vapor deposition processes, crystal growth, and material growth, which can be achieved by using the ultra-high purity SiC and SiOC new materials disclosed and taught in the concurrently filed serial number 14 / 864,539 patent application (U.S. publication number 2016 / 0208412), serial number 14 / 864,125 patent application (U.S. publication number 2016 / 0207782), and PCT / US2015 / 051997 patent application (publication number WO 2016 / 049344), and the entire disclosure of each patent is incorporated into the present application by reference.
[0004] Related cross references
[0005] This application: (i) claims the benefit of U.S. Provisional Application Serial No. 62 / 232,355, filed September 24, 2015, under 35 U.S.C. § 119(e)(1), the entire disclosure of each of which is incorporated herein by reference. Background Art
[0006] The use of these materials with 6-9, 7-9, 8-9 and higher purities provides many advantages for the vapor deposition growth of crystals and provides new and sophisticated vapor deposition apparatus and systems for crystal growth. The ultra-high purity materials provide: faster crystal growth, the ability to grow larger and purer seed crystals or starting plates for the deposition process, and the utilization of a higher percentage of starting material in the apparatus. Therefore, the use of high purity and ultra-high purity materials in vapor deposition techniques can enhance control and achieve higher efficiency.
[0007] In recent years, the demand for high-purity silicon carbide, especially for high-purity single crystalline carbide materials for end products such as semiconductors, has been increasing, but it cannot be met. For example, Wang et al. pointed out in Synthesis of High Power Sic Powder for High-resistivity SiC Single crystals Growth, p.118 (J. Mater. Sic. Technol. Vol. 23, No 1, 2007) (hereinafter referred to as Wang p.118): "Single crystals are increasingly important as substrates in high-frequency and high-power silicon carbide electronic devices" (translation). In order to obtain these high-purity silicon carbide products, the silicon carbide powder used as the starting or raw material must be extremely pure. "However, Wang et al. pointed out in the above report: "Commercially available SiC powder is usually synthesized by carbothermal reduction of silica. Unfortunately, it is usually contaminated to be unsuitable for SiC growth" (translation).
[0008] The long-standing need for high-purity silicon carbide and the difficulty that the existing technology does not provide a feasible method for obtaining this material (from both a technical and economic point of view) are also recognized in Zwieback et al. Patent No. 2013 / 0309496 (hereinafter referred to as Zwieback), which states that "In general, the availability of high-purity SiC raw materials is very important for the growth of SiC single crystals, and is crucial for semi-insulating SiC crystals" (translation) (Zwieback paragraph 7). Zwieback further points out that existing methods, including liquid based methods, have always been unable to meet this demand: "Although many improvements to the Acheson process have been developed over the years, the SiC materials produced always contain high concentrations of boron, nitrogen, aluminum, and other metals and are not suitable as raw materials for growing SiC crystals for semiconductor materials" (translation) (Zwieback, paragraph 9); "Commercial-grade bulk SiC produced by CVD is not pure enough to be used as a source for growing SiC crystals" (translation) (Zwieback, paragraph 10); "SiC materials produced by liquid processes contain high concentrations of contaminants and are not suitable for growing SiC crystals for semiconductor materials" (translation) (Zwieback, paragraph 11); and direct synthesis of SiC will produce impurities that "prevent the use of the material" (translation) (Zwieback, paragraph 15). Zwieback attempts to provide high-purity SiC to meet the long-standing demand for SiC materials through a complex, multi-step method that appears to be a direct production process. This process is believed to be neither technically nor economically feasible and therefore cannot meet the long-standing demand for commercial-grade high-purity SiC.
[0009] Thus, although methods for obtaining silicon carbide are known, none of these methods is believed to provide the necessary technical, productivity, and economic feasibility to meet the purity, quantity, and low cost required for commercial use and applications, especially to meet the growing demand for semiconductor-grade materials, as well as other commercial uses and applications that are in development. Wang et al. pointed out: "Among these synthesis methods, only CVD has been successfully used to produce high-purity SiC powders, but the high cost of its technology makes it unsuitable for large-scale production" (translation) (Wang p.118).
[0010] CVD usually refers to Chemical Vapor Deposition. CVD is a vapor deposition technology. In addition to CVD, vapor deposition technologies also include PVD (Physical Vapor Deposition), plasma enhanced CVD (plasma enhanced CVD), PVT (Physical Vapor Transport), etc.
[0011] Therefore, for these finished products and applications requiring high purity raw materials, there is an increasing need for low-cost silicon carbide raw materials with a purity of at least about 99.9%, 99.99%, 99.999%, 99.9999%, and 99.99999% or higher. However, this is earlier than the embodiments disclosed and taught in the serial number 14 / 864,539 patent application (U.S. Publication No. 2016 / 0208412), the serial number 14 / 864,125 patent application (U.S. Publication No. 2016 / 0207782), and the PCT / US2015 / 051997 patent application (Publication No. WO2016 / 049344). In fact, this demand has not been met.
[0012] Furthermore, prior to the embodiments of the invention disclosed and taught in patent application Ser. No. 14 / 864,539 (U.S. Publication No. 2016 / 0208412), patent application Ser. No. 14 / 864,125 (U.S. Publication No. 2016 / 0207782), and patent application PCT / US2015 / 051997 (Publication No. WO 2016 / 049344), it is believed that production of high purity and ultra-high purity SiOC materials in quantities of only a few ounces in smaller laboratory batches has been unavailable, and the importance and benefits of, and the need for, such materials have been largely overlooked.
[0013] High-purity single-crystal silicon carbide material has many favorable characteristics and properties. For example, it has a Young's modulus of 424 GPa and is very hard. Polycrystalline silicon carbide also has extremely high hardness, which depends on the particle structure and other factors.
[0014] In this document, unless otherwise specified, the term "specific gravity", also known as apparent density, has the broadest possible interpretation in this application and generally refers to the weight per unit volume of a structure (i.e., the volumetric shape of a material). The material includes the internal porosity of its particles in its volume. It can be measured by a low-viscosity liquid that wets the surface of the particles.
[0015] In this document, unless otherwise specified, the term "actual density", also known as true density, has the broadest possible interpretation in this application and generally refers to the weight per unit volume of a structure without voids in the material. This measurement and material substantially excludes any internal pores in the material, that is, the material does not contain any voids.
[0016] Therefore, a batch of porous foam balls (i.e. The weight of the balls filled in the container corresponds to the volume density of the balls:
[0017]
[0018] The weight per volume of a single sphere is its apparent density:
[0019]
[0020] After all the voids in the ball have been removed, the weight of the material that makes up the ball's skeleton per remaining volume is the actual density:
[0021]
[0022] In this document, unless otherwise specified, room temperature is 25° C. Meanwhile, standard ambient temperature and pressure are 25° C. and 1 atmosphere.
[0023] In general, unless otherwise specified, the term "about" herein is intended to encompass a range of variation of ±10%, experimental or instrument error, and preferably encompasses a wider range.
[0024] In addition, the Unless otherwise specified, it refers to the microtubule density less than or equal to a certain value, where means less than or equal to, for example, cm-2 refers to less than or equal to 100 microtubes / cm 2 of microtubule density. Summary of the invention
[0025] There has been a long-standing and unmet need for improved methods of growing vapor deposited SiC crystals.
[0026] The present invention addresses this need through the compositions, materials, articles of manufacture, devices, and processes disclosed, taught, and claimed herein.
[0027] In addition, the present invention also provides compositions, methods and articles having one or more of the following characteristics: a silicon carbide having a volume shape containing less than about 50 ppm of an element selected from the group consisting of Al, Fe, B and P; a silicon carbide having a volume shape containing less than about 40 ppm of an element selected from the group consisting of Al, Fe, B and P; a silicon carbide having a volume shape containing less than about 100 ppm of an element selected from the group consisting of Al, Fe, B and P; a silicon carbide having a volume shape containing less than about 1000 ppm of an element selected from the group consisting of Al, Fe, B and P; a silicon carbide having a volume shape containing less than about 50 ppm of an element selected from the group consisting of Ti, Al, Fe, B, P, Pt, Ca, Mg, Li and Na; a silicon carbide having a volume shape containing less than about 50 ppm of an element selected from the group consisting of Al, Fe, B, P, Pt, Ca, Mg, Li, Na, Ni, V, elements selected from the group consisting of Pr, Ce, Cr, S and As; a silicon carbide having a volume form containing less than about 50 ppm of elements selected from the group consisting of Al, Fe, B, P, Pt, Ca, Mg, Li, Na, Ni, V, Ti, Ce, Cr, S and As; and a silicon carbide having a volume form containing less than about 50 ppm of elements selected from the group consisting of Al, Fe, B, P, Pt, Ca, Mg, Li, Na, Ni, V, Pr, Ce, Cr, S and As.
[0028] In addition, the present invention also provides compositions, methods and articles having one or more of the following characteristics: the silicon carbide has less than about 90 ppm of elements selected from the group consisting of Ti, Al, Fe, B, P, Pt, Ca, Ce, Cr, S and As; the silicon carbide has less than about 90 ppm of elements selected from the group consisting of Ti, Fe, P, Pt, Ca, Mg, Li, Na, Ni, Cr and As; the silicon carbide has less than about 90 ppm of elements selected from the group consisting of Al, Fe, B, P, Mg, Li, V, Ce, Cr and S; the silicon carbide has less than about 90 ppm of elements selected from the group consisting of Al, Fe, B and P; the silicon carbide has less than about 90 ppm of elements selected from the group consisting of Ti, Al, Fe, B, P, Pt, Ca, Ce, Cr, S and As; the silicon carbide has less than about 90 ppm of elements selected from the group consisting of Ti, Fe, P, Pt, Ca, Mg, Li, Na, Ni, Cr and As; the silicon carbide has less than about 90 ppm of an element selected from the group consisting of Al, Fe, B, P, Mg, Li, V, Ce, Cr and S; and the produced silicon carbide is at least 99.9999% pure; and the silicon carbide is beta type.
[0029] Accordingly, the present invention provides a high purity polymer-derived ceramic SiC composition, the composition comprising: a SiC4 structural configuration; a composition having a defined surface, wherein the surface of the composition is resistant to oxidation at standard ambient temperature and pressure, and thus the surface is substantially free of an oxide layer at standard ambient temperature and pressure; and the composition is substantially free of impurities, wherein the total impurity content is less than 1 ppm.
[0030] The present invention provides compositions, methods and articles having one or more of the following characteristics: the SiC4 structural configuration is selected from the group consisting of a cubic structure and a tetrahedral structure; the SiC4 structural configuration is selected from the group consisting of a hexagonal, rhombohedral and trigonal structure; the SiC 4The structure is selected from the group consisting of 3C-SiC, β-SiC, 2H-SiC, 4H-SiC, 6H-SiC, 8H, 10H, 16H, 18H, 19H, 15R, 21R, 24H, 33R, 39R, 27R, 48H and 51R; the SiC4 structure is selected from the group consisting of stacking sequences ABCABC, ABAB, ABCBABCB and ABCACBABCACB.
[0031] In addition, the present invention further provides a semiconductor comprising a SiC wafer prepared from a high purity polymer-derived ceramic SiC composition having a band gap, wherein the band gap is from about 2.26 eV to about 3.33 eV.
[0032] The present invention still further provides a semiconductor comprising a SiC wafer prepared from a high purity polymer derived ceramic SiC composition having a band gap greater than about 2.20 eV.
[0033] The present invention still further provides a semiconductor comprising a SiC wafer prepared from a high purity polymer derived ceramic SiC composition having a band gap of about 2.26 eV to about 3.33 eV.
[0034] The present invention further provides a power device, comprising a ceramic SiC composition having E max SiC wafer, wherein the E max Greater than about 1 MV / cm.
[0035] The present invention further provides a power device comprising a ceramic SiC composition having E max SiC wafer, wherein the E max Greater than about 1.5 MV / cm.
[0036] The present invention further provides a power device comprising a ceramic SiC composition having E max SiC wafer, wherein the E max Greater than about 2 MV / cm.
[0037] The present invention further provides a power device comprising a ceramic SiC composition having E max SiC wafer, wherein the E max Greater than about 2.5 MV / cm.
[0038] In addition, the present invention provides a high frequency device comprising a 2×10 7 cm / sec 2 Saturation drift velocity of SiC wafers.
[0039] In addition, the present invention further provides an article having thermal conductivity made from a high purity polymer-derived ceramic SiC composition, wherein the thermal conductivity is greater than about 4.0 W / (cm·K) at room temperature.
[0040] The present invention further provides an industrial article made from a high purity polymer derived ceramic SiC composition having a thermal conductivity greater than about 4.5 W / (cm·K) at room temperature.
[0041] In addition, the present invention provides methods, compositions and articles having one or more of the following characteristics: a surface defined by the volumetric shape, wherein the surface is substantially free of an oxide layer; wherein the volumetric shape is selected from the group consisting of pucks, briquettes, bricks, pellets, discs, pills and tablets; the elastic modulus of the volumetric shape is less than about 100 GPa, and the compressive strength is less than about 1,000 MPa; the elastic modulus of the volumetric shape is less than about 100 GPa, and the compressive strength is less than about 1,000 MPa; the elastic modulus of the volumetric shape is less than about 10 GPa, and the compressive strength is less than about 500 MPa; the elastic modulus of the volumetric shape is less than about 10 GPa, and the compressive strength is less than about 500 MPa; the elastic modulus of the volumetric shape is less than about 10 GPa, and the compressive strength is less than about 500 MPa; the friable mass (friable mass) having an impurity content of less than about 1 ppm mass); a fragile group of SiC4 structure configuration selected from the group consisting of cubic structure and tetragonal structure; a fragile group of SiC4 structure configuration selected from the group consisting of hexagonal, rhombohedral and trigonal structures; a fragile group of SiC4 structure configuration selected from the group consisting of 3C-SiC, β-SiC, 2H-SiC, 4H-SiC, 6H-SiC, 8H, 10H, 16H, 18H, 19H, 15R, 21R, 24H, 33R, 39R, 27R, 48H and 51R; a fragile group of SiC4 structure configuration selected from the group consisting of stacking sequence ABCABC, ABAB, ABCBABCB and ABCACBABCACB; and, a fragile group of SiC4 structure configuration selected from the group consisting of stacking sequence ABCABC, ABAB and ABCBABCB.
[0042] In addition, the present invention also provides an epitaxial polysilicon carbide (polysilocarb) derived SiC layer on a substrate, wherein the epitaxial polysilicon carbide derived SiC layer is prepared from: a high-purity polymer-derived ceramic SiC composition, which includes: a SiC4 structural configuration; a composition defining a surface, wherein the surface of the composition is resistant to oxidation at standard ambient temperature and pressure, and thus the surface is substantially free of an oxide layer at standard ambient temperature and pressure; and, the composition is substantially free of impurities, with a total impurity content of less than 1 ppm, and thus the epitaxial polysilicon carbide derived SiC is substantially free of impurities, with an impurity content of less than 1 ppm.
[0043] In addition, the present invention also provides methods, compositions and articles having one or more of the following characteristics: The impurities are selected from the group consisting of Al, Fe, B, P, Pt, Ca, Mg, Li, Na, Ni, V, Ti, Ce, Cr, S and As; the impurities are selected from the group consisting of Al, Fe, B, P, Pt, Ca, Mg, Li, Na, Ni, V, Ti, Ce, Cr, S and As; the impurities are selected from the group consisting of Al, Fe, B, P and N; the impurities are selected from the group consisting of Al, Fe, B, P and Na; the impurities are selected from the group consisting of Al, Fe, B, P and Na; the impurities are selected from the group consisting of Al, B and P; the substrate comprises SiC; and, the substrate comprises Si; the substrate comprises a tie layer and SiOC.
[0044] In addition, the present invention also provides an epitaxial polysilicon carbide derived SiC layer located on a substrate, wherein the epitaxial polysilicon carbide derived SiC layer is prepared from: high-purity polymer-derived ceramic SiC, which includes: polymer-derived SiC granular particles, wherein the particles include a SiC4 structural configuration; the granular particles define a volume shape; the granular particles have an actual density of about 3.0 to about 3.5 g / cc, an elastic modulus of about 410 GPa, and a compressive strength of about 3,900 MPa; the volume shape has an apparent density of less than about 2.5 g / cc, an elastic modulus of less than about 205 GPa, and a compressive strength of less than about 2,000 MPa; and the volume shape is substantially free of impurities, and the total impurities are selected from the group consisting of Al, Fe and B, and are less than 10 ppm.
[0045] In addition, the present invention also provides a polysilicon carbide derived SiC pear-shaped crystal, comprising: the polysilicon carbide derived SiC pear-shaped crystal having a defined length and a diameter, wherein the length is greater than about 1 inch and the diameter is greater than about 2 inches; the polysilicon carbide derived pear-shaped crystal is produced from vapor deposition of a high-purity polymer-derived ceramic SiC composition, wherein the composition characteristics include: a SiC4 structural configuration; the composition having a defined surface, wherein the surface of the composition is resistant to oxidation at standard ambient temperature and pressure, and thus the surface is substantially free of an oxide layer at standard ambient temperature and pressure; and the composition is substantially free of impurities, with a total impurity content of less than 1 ppm, and thus the polysilicon carbide derived SiC pear-shaped crystal is substantially free of impurities, with an impurity content of less than 1 ppm, and substantially free of micropipes.
[0046] In addition, the present invention also provides methods, compositions and articles having one or more of the following features: a polysilicon oxycarbide derived SiC pear-shaped crystal having a length of at least 3 inches; a polysilicon oxycarbide derived SiC pear-shaped crystal having a length of at least 5 inches; a polysilicon oxycarbide derived SiC pear-shaped crystal having a length of at least 8 inches; a polysilicon oxycarbide derived SiC pear-shaped crystal having a length of at least 12 inches; a polysilicon oxycarbide derived SiC pear-shaped crystal having a diameter of at least 4 inches; a polysilicon oxycarbide derived SiC pear-shaped crystal having a diameter of at least 8 inches; a polysilicon oxycarbide derived SiC pear-shaped crystal having a diameter of at least 10 inches; a polysilicon oxycarbide derived SiC pear-shaped crystal having a diameter of at least 12 inches; a polysilicon oxycarbide derived SiC pear-shaped crystal having a diameter of at least 9 inches and a length of at least 4 inches; a polysilicon oxycarbide derived SiC pear-shaped crystal having a diameter of at least 10 inches and a length of at least 4 inches; a polysilicon oxycarbide derived SiC pear-shaped crystal having a diameter of at least 12 inches and a length of at least 4 inches; and, a polysilicon oxycarbide derived SiC pear-shaped crystal having a diameter of at least 11 inches and a length of at least 4 inches.
[0047] In addition, the present invention also provides a polysilicon carbide derived SiC pear-shaped crystal, comprising: the polysilicon carbide derived SiC pear-shaped crystal having a defined length and a diameter, wherein the length is greater than about 1 inch and the diameter is greater than 2 inches; the polysilicon carbide derived SiC pear-shaped crystal is produced from the vapor deposition of a high-purity polymer-derived ceramic SiC friable mass, the friable mass comprising: polymer-derived SiC granular particles, which include a SiC4 structural configuration; the granular particles defining a volume shape; the granular particles having an actual density of about 3.0 to about 3.5 g / cc, an elastic modulus of about 410 GPa, and a compressive strength of about 3,900 MPa; and, the volume shape having an apparent density of less than about 2.0 g / cc, an elastic modulus of less than about 100 GPa, and a compressive strength of less than about 1,000 MPa; the volume shape is substantially free of impurities, and the total impurities are selected from Al, The polysilicon oxycarbide derived SiC pear-shaped crystals contain substantially no micropipes.
[0048] The present invention further provides a polysilicon oxide carbide derived SiC pear-shaped crystal: the pear-shaped crystal has a microtube / cm 2 Value; The pear-shaped crystal has less than 1 microtube / cm 2 Value; The pear-shaped crystal has less than 0.5 microtubes / cm 2 Value; The pear-shaped crystal has less than 0.1 microtubes / cm 2 value.
[0049] In addition, the present invention also provides a method for preparing polysilicon carbide-derived SiC pear-shaped crystals, and the polysilicon carbide-derived SiC pear-shaped crystals having a defined length and a diameter, wherein the length is greater than about 1 inch and the diameter is greater than about 2 inches, the method comprising: the polysilicon carbide-derived SiC pear-shaped crystals are produced from vapor deposition of a high-purity polymer-derived ceramic SiC mass, the mass comprising: polymer-derived SiC granular particles, the granular particles comprising a SiC4 structural configuration; the granular particles defining a volumetric shape; the granular particles having an actual density of about 3.0 to about 3.5 g / cc, an elastic modulus of about 410 GPa, and a compressive strength of about 3,900 MPa; and the volumetric shape having a bulk density of less than about 2.0 g / cc, an elastic modulus of less than about 100 GPa, and a compressive strength of less than about 1,000 MPa; the volumetric shape is substantially free of impurities, the total impurities of which are selected from the group consisting of Al, Fe, and B, and are less than 10 ppm; and, The polysilicon oxide carbide derived SiC pear-shaped crystal has less than 1 microtube / cm 2 value.
[0050] In addition, the present invention also provides a method for preparing a polysilicon carbide-derived SiC pear-shaped crystal, and the polysilicon carbide-derived SiC pear-shaped crystal having a defined length and a diameter, wherein the length is greater than about 1 inch and the diameter is greater than about 2 inches, the method comprising: the polysilicon carbide-derived SiC pear-shaped crystal is produced from a vapor deposition of a high-purity polymer-derived ceramic SiC friable mass, the friable mass comprising: polymer-derived SiC granular particles, the granular particles comprising a SiC4 structural configuration; the granular particles defining a volume shape; having a mass of about 3.0 to about 3.5 g / cc The granular particles have an actual density of about 410 GPa, an elastic modulus of about 410 GPa, and a compressive strength of about 3,900 MPa; and the bulk shape has an apparent density of less than about 2.0 g / cc, an elastic modulus of less than about 100 GPa, and a compressive strength of less than about 1,000 MPa; the bulk shape is substantially free of impurities, and the total impurities are selected from the group consisting of Al, Fe, B, P, Ca, Mg, Na, Ni, Cr, S and As, and are less than 10 ppm; and the polysilicon carbide derived SiC pear-shaped crystals are substantially free of micropipes.
[0051] Next, the present invention provides a method for preparing high-purity silicon oxycarbide, the method comprising: distilling a liquid containing silicon, carbon and oxygen; and solidifying the liquid into a solidified material; wherein the solidified material is at least 99.999% pure.
[0052] Next, the present invention provides a method for preparing a pear-shaped crystal for producing a silicon carbide wafer, wherein the silicon carbide wafer is characterized by the following properties:
[0053] 2 inches 6H N type,
[0054] 6H-N 2 inch diameter,
[0055] Type / dopant: N / nitrogen,
[0056] Crystal orientation: <0001> + / -0.5 degrees,
[0057] Thickness: 330±25um D grade,
[0058] cm-2D level,
[0059] Resistivity: 0.02-0.2Ω·cm;
[0060] The method comprises:
[0061] forming a vapor of a polymer derived ceramic SiC having a purity of at least about 6 nines and being free of an oxide layer,
[0062] depositing the vapor onto a seed crystal to form a pear-shaped crystal, and
[0063] The pear-shaped crystal is provided to a wafer preparation process.
[0064] In addition, the present invention provides the method, pear-shaped crystal and wafer having one or more of the following characteristics: the seed crystal comprises polymer-derived ceramic SiC; the wafer preparation process produces a wafer having improved characteristics relative to SiC material derived from a non-polymer; and the improved characteristics are selected from the group consisting of bow, edge contour, flatness, focal plane, warp and site flatness.
[0065] The present invention further provides a method for preparing a silicon carbide wafer, the method comprising the steps of generating vapor of polymer-derived ceramic SiC having a purity of at least about 6 nines and containing no oxide layer, depositing the vapor on a seed crystal to produce a pear-shaped crystal, and providing the pear-shaped crystal for a wafer preparation process.
[0066] Additionally, the present invention provides a method for preparing wafers from a polymer derived ceramic starting material, wherein the wafers are characterized as having a 2"-10" 6H N-type property.
[0067] The present invention further provides a method for preparing a pear-shaped crystal for producing a silicon carbide wafer, wherein the silicon carbide wafer is characterized by the following properties:
[0068] 4H-N 2 to 10 inches diameter,
[0069] Type / dopant: N / nitrogen,
[0070] Crystal orientation: <0001> + / -0.5 degrees,
[0071] Thickness: 330±25um Class B,
[0072] cm-2B level,
[0073] Resistivity: 0.01-0.1Ω·cm Class B,
[0074] Curvature / warpage / TTV<25μm;
[0075] The method comprises:
[0076] forming a vapor of a polymer derived ceramic SiC having a purity of at least about 6 nines and being free of an oxide layer,
[0077] depositing the vapor onto a seed crystal to form a pear-shaped crystal, and
[0078] The pear-shaped crystal is provided to a wafer preparation process.
[0079] Next, the present invention provides a method for preparing a pear-shaped crystal for producing a silicon carbide wafer, wherein the silicon carbide wafer is characterized by the following properties:
[0080] 2 inches 6H N type,
[0081] 6H-N 2 inch diameter,
[0082] Type / dopant: N / nitrogen,
[0083] Crystal orientation: <0001> + / -0.5 degrees,
[0084] Thickness: 330±25um D grade,
[0085] cm-2D level,
[0086] Resistivity: 0.02-0.2Ω·cm;
[0087] The method comprises:
[0088] forming a vapor of a polymer derived ceramic SiC, the polymer derived ceramic having a purity of at least about 6 nines,
[0089] depositing the vapor onto a seed crystal to form a pear-shaped crystal, and
[0090] The pear-shaped crystal is provided to a wafer preparation process.
[0091] The present invention further provides a method for preparing a silicon carbide wafer, the method comprising the steps of:
[0092] forming a vapor of a polymer derived ceramic SiC, the polymer derived ceramic having a purity of at least about 6 nines,
[0093] depositing the vapor onto a seed crystal to form a pear-shaped crystal, and
[0094] The pear-shaped crystal is provided to a wafer preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0095] Figure 1 FIG. 4 is a schematic cross-sectional view of a vapor deposition apparatus using ultra-high purity SiC or SiOC material according to the present invention.
[0096] Figure 2 According to the present invention Figure 1 A more detailed cross-sectional schematic diagram of a vapor deposition apparatus utilizing ultra-high purity SiC or SiOC material.
[0097] Figure 3 FIG. 4 is a schematic cross-sectional view of a vapor deposition apparatus using ultra-high purity SiC or SiOC material according to the present invention.
[0098] Figure 4 FIG. 4 is a schematic cross-sectional view of a vapor deposition apparatus using ultra-high purity SiC or SiOC material according to the present invention.
[0099] Figure 5a , 5b 5c is a cross-sectional schematic diagram of a vapor deposition device using ultra-high purity SiC or SiOC material according to the present invention.
[0100] Figure 6 FIG. 4 is a schematic cross-sectional view of a vapor deposition apparatus using ultra-high purity SiC or SiOC material according to the present invention.
[0101] Figure 7 FIG. 4 is a schematic cross-sectional view of a vapor deposition apparatus using ultra-high purity SiC or SiOC material according to the present invention.
[0102] Figure 8 FIG. 4 is a schematic cross-sectional view of a vapor deposition apparatus using ultra-high purity SiC or SiOC material according to the present invention.
[0103] Fig. 9FIG. 4 is a schematic cross-sectional view of a vapor deposition apparatus using ultra-high purity SiC or SiOC material according to the present invention.
[0104] Fig.10 FIG. 4 is a schematic cross-sectional view of a vapor deposition apparatus using ultra-high purity SiC or SiOC material according to the present invention.
[0105] Fig.11 Schematic cross-sectional view of a vapor deposition device according to the present invention.
[0106] Fig.12 Schematic cross-sectional view of a vapor deposition device according to the present invention.
[0107] Fig.13 Schematic cross-sectional view of a vapor deposition device according to the present invention.
[0108] Fig.14 For SiC, Si 2 C and SiC 2 Voltage division diagram. DETAILED DESCRIPTION
[0109] Generally, the present invention relates to vapor deposition techniques and vapor deposition apparatus using fine, high and ultra-high purity polysilicon oxycarbide (SiOC) and silicon carbide (SiC).
[0110] Examples of vapor deposition techniques and devices include: CVD usually refers to chemical vapor deposition, which is a vapor deposition technique. In addition to CVD, vapor deposition techniques also include PVD (physical vapor deposition), plasma enhanced CVD, PVT (physical vapor transport), etc.
[0111] In general, the present invention is directed to "polysilicon oxycarbide" materials, i.e., materials containing silicon (Si), oxygen (O) and carbon (C), and materials converted from such materials into various SiC forms. Polysilicon oxycarbide materials may also contain other elements. Polysilicon oxycarbide materials are produced from one or more polysilicon oxycarbide precursor formulations or precursor formulations. The polysilicon oxycarbide precursor formulation contains one or more functionalized silicon polymers or monomers, and potentially also includes other ingredients, such as inhibitors, catalysts, initiators, modifiers, dopants, and combinations and variations thereof with other materials and additives. Silicon oxycarbide materials, or SiOC compositions and other similar terms, unless otherwise specified, refer to polysilicon oxycarbide materials that are cured into plastic or solid materials containing Si, O and C, and polysilicon oxycarbide materials that are pyrolyzed into ceramic materials containing Si, O and C.
[0112] Typically and preferably, the polysilicon carbide precursor formulation is initially liquid. The liquid polysilicon carbide precursor formulation is then cured to a solid or semi-solid material (i.e., a plastic). A partially cured material may be provided by initially curing the polysilicon carbide precursor formulation, which also refers to a preform, an unformed material, or a cured object. The unformed material may be further cured. Thus, its production process may require one or more curing steps. The material may be "end cured," meaning that the material is cured to have the necessary physical strength and other properties required for the intended use. The material may be cured to a degree of "final cure" or "hard cure," meaning that the chemical reaction is completely or substantially stopped (e.g., in terms of measurement, the disappearance of a reactant group in the material, or a leveling off of a decrease in a reactant group over time). Thus, the material may be cured to varying degrees depending on its intended use, for example, in some cases, "end cure" and "final cure" may be the same.
[0113] The curing can be carried out at standard ambient temperature and pressure (SATP, 1 atmosphere, 25°C), above or below standard ambient temperature, above or below standard ambient pressure, and can also be carried out for different time periods (continuous and cyclic, such as alternating heating and cooling): from less than 1 minute to several minutes, hours or days (or longer). The curing can also be carried out in air, liquid or a preselected atmosphere (such as argon or nitrogen).
[0114] Metal alkoxides may also be used to provide metal functionality to the precursor formulation and product. Metal alkoxide compounds may be mixed with silicon precursor compounds and then treated with water to produce oxides while the heteromolecules polymerize into polymers. This process may also be accomplished using metal halides and metalamides. Preferably, this process may be accomplished using early transition metals: aluminum, gallium, and indium, later transition metals: Fe, Mn, and Cu, and alkaline earth metals: Ca, Sr, Ba, and Mg.
[0115] Compounds in which Si is directly bonded to a metal center stabilized by a halide or an organic group may also be used to provide metal functionality to precursor formulations and products.
[0116] In addition, it should be understood that the metal and metal composites described above can be a continuous phase after pyrolysis or subsequent heat treatment. Specific formulations can be designed to react with selected metals to produce metal carbides, metal oxides and other metal compounds in situ, which are generally referred to as cermets (e.g., ceramic metal compounds). The formulation can react with selected metals to produce in situ compounds such as mullite and alumino silicate. The metal content of the formulation or final product relative to the silicon content can be about 0.1 to 99.9 mol%, about 1 mol% or more, about 10 mol% or more, and about 20 mol% or more. The predetermined stoichiometry can be controlled and provided by abandoning the use of the precursor formulation and the metal.
[0117] The polysilicon oxycarbide can also be used as a binder in composite structures, such as a binder for metals, ceramics and inorganic substrates.
[0118] In this document, unless otherwise specified, "%", "weight %" and "mass %" are used interchangeably and all refer to the percentage of the weight of the first component to the total weight of the formulation, mixture, material or product, etc. In this document, unless otherwise specified, "volume %" and "volume %" are the same and all refer to the percentage of the volume of the first component to the total volume of the formulation, mixture, material or product, etc.
[0119] At various points in the manufacturing process, the polysilicon oxide carbide structures, intermediates, final products, and combinations and variations thereof, can be machined, ground, molded, shaped, or drilled, or mechanically processed and shaped.
[0120] Customized and predetermined control over when chemical reactions are performed at different stages of the process from raw materials to final product can provide benefits including reduced costs, improved process control, improved reliability, improved efficiency, improved product characteristics, improved purity, etc. and combinations and variations thereof. The sequencing of chemical reactions can be based primarily on the processing and preparation of precursors and precursor formulations, and can also be based on curing and pyrolysis conditions. Further, the customized and predetermined selection of chemical reaction steps, formulations and conditions can enhance product and process characteristics through preferably predetermined and controlled chemical reactions, molecular arrangements and rearrangements, and microstructural arrangements and rearrangements.
[0121] The ability to start with a liquid material containing substantially all of the building blocks (e.g., Si and C) required to make SiC can provide significant benefits for controlling impurities, contamination, and making high purity SiOC (which can be converted to high purity SiC, or can be made directly by a single combined process or step). Thus, embodiments of the present invention provide for the preparation of SiOC having a purity of at least about 99.9% (3 nines), about 99.99% (4 nines), about 99.999% (5 nines), about 99.9999% (6 nines), and about 99.99999% (7 nines) or more. Similarly, embodiments of the present invention also provide for the preparation of SiC having a purity of at least about 99.9% (3 nines), about 99.99% (4 nines), about 99.999% (5 nines), about 99.9999% (6 nines), and about 99.99999% (7 nines) or more. The above purity values are based on the amount of SiOC or SiC relative to the total material contained in a given SiOC or SiC product sample.
[0122] Embodiments of polysilicon oxycarbide derived SiC and processes for making the same of the present invention reduce the cost of providing high purity and ultra-high purity SiC while increasing the purity obtained. Thus, among other aspects, embodiments of polysilicon oxycarbide derived SiC materials and articles of the present invention reduce costs and improve product properties compared to existing SiC, SiOC and Si materials and products. Thus, among other aspects, embodiments of polysilicon oxycarbide derived SiC materials and articles of the present invention can replace existing SiC and Si materials and products in many applications and have the ability to provide new and improved applications that are not obtainable with existing SiC and Si materials and products due to technical and economic factors.
[0123] Embodiments of the polymer derived SiC wafers of the present invention include: wafers having diameters of about 2 inches, about 3 inches, about 4 inches, about 5 inches, about 6 inches, about 7 inches, about 12 inches, about 2 to about 8 inches, about 4 to about 6 inches, and possibly larger diameters; square, round, and other shapes; surface areas per side of about 1 square inch, about 4 square inches, about 10 square inches, and larger and smaller; thicknesses of about 100 μm, about 200 μm, about 300 μm, about 500 μm, about 700 μm, about 50 to about 800 μm, about 100 to about 700 μm, about 100 to about 400 μm, and larger or smaller; and combinations and variations of the above.
[0124] In embodiments of the present invention, the high purity SiC contains low, very low and sub-detectable amounts of materials (or considered impurities) that may cause serious problems in subsequent processing and preparation of, for example, pear-shaped crystals, wafers, electronic components, optical components and other SiC-based intermediates and final products.
[0125] Thus, the polymer derived high purity SiC, and especially the polysilicon oxycarbide derived high purity SiOC, and the high purity SiC converted from the SiOC, of the present invention have a purity of at least about 99.9%, at least about 99.99%, at least about 99.999%, at least about 99.9999%, and at least about 99.99999% or higher. In addition, it should be noted that embodiments of the present invention include polymer derived SiC of any purity level, and SiOC of any purity level, including low purity levels such as 99.0%, 95%, 90% and lower. The lower purity embodiments described above have and will find substantial uses and applications. Similarly, the high purity SiC described above will also find uses and applications, and will provide new and unexpected benefits to applications previously limited to Si or other non-SiC materials.
[0126] Embodiments of the present invention include the use of high purity SiC in the preparation of wafers for electronic products and semiconductor applications. High purity SiC is required in the vapor deposition apparatus and processing for preparing pear-shaped crystals and wafers for subsequent use. Specifically, as shown in Table 3, embodiments of high purity polymer derived SiOC and SiC may preferably have one, more, and all of the elements in Table 3, which are considered impurities in certain vapor deposition apparatus, electronic applications, and semiconductor applications. Therefore, the polysilicon oxide carbide derived SiC in embodiments of the present invention may be free of impurities, substantially free of impurities, and may contain some but not more than the amount of impurities shown in Table 3.
[0127] Table 3
[0128]
[0129] In one embodiment, Pr is also considered as an impurity in some applications, if so, the impurity content range shown in Table 3 may be applicable to Pr.
[0130] Unless otherwise specified, in this document, "high purity", "% purity", "% impurity" and similar terms will be used when referring to purity; excess carbon, that is, carbon in excess of the stoichiometric amount of SiC, is not included, referenced, considered or used in subsequent calculations and material characterization. In some applications, excess carbon does not affect the application or product and is therefore not considered an impurity. In other applications, excess carbon can also be beneficial, for example, carbon can be used as a sintering aid; excess carbon can be used to handle and compensate for irregularities in vapor deposition equipment and processing.
[0131] In some applications where nitrogen is considered a contaminant, polysilicon oxycarbide derived SiC and SiOC of embodiments of the present invention may contain less than about 1000 ppm, less than about 100 ppm, less than about 10 ppm, less than about 1 ppm, less than about 0.1 ppm, and lower nitrogen.
[0132] In one embodiment of the polysilicon oxycarbide derived SiC of the present invention, it is substantially free of oxygen in any form, whether bound to Si or C, or as an oxide layer. Thus, embodiments of the polysilicon oxycarbide derived SiC of the present invention may contain less than about 1000 ppm, less than about 100 ppm, less than about 10 ppm, less than about 1 ppm, less than about 0.1 ppm, and less oxygen. The silicon oxycarbide derived SiC is resistant to oxidation when exposed to air at standard temperature and pressure, and does not form an oxide layer. The oxide layer-free SiC stored under ambient conditions can provide benefits to subsequent manufacturing processes, where the oxide layer can be considered an impurity or a detriment to the manufacturing process.
[0133] The polysilicon oxycarbide derived SiC embodiments of the present invention are highly versatile materials that can have a variety of forms, such as amorphous, crystalline with many different crystalline forms, single crystals, and polycrystalline. A single batch, volume shape, or sample of polysilicon oxycarbide derived SiC has one or more of the above forms, as well as various combinations and variations thereof. Therefore, the polysilicon oxycarbide derived SiC materials of the present invention can be used in other applications, including abrasive materials, friction components, optical components, bulletproof and impact-resistant materials, insulation materials, and electronic products, etc.
[0134] Polysilicon carbide derived SiC powders, fines, pellets or other smaller sized shapes can be interconnected by sintering operations to form components and structures.
[0135] The interconnection, such as stamping, sintering, ready-to-press, etc., of the polymer-derived SiC embodiments of the present invention may be accomplished by any conventional processing, and may also be accomplished by using sintering aids and other additives used in conventional processing. The ultra-high purity polymer-derived SiC embodiments of the present invention provide a unique SiC that has never been seen before, and the ability to interconnect its particles without the need for any sintering aids or processing additives. Thus, the ultra-high purity SiC of the present invention can self-sinter, i.e., it does not require any sintering aids or other additives to form a solid and preferably integral solid shape through its bonding or other forming methods (e.g., sintering, stamping). Thus, the self-sintered SiC shape is 2, 3, 4 times or more stronger than a similar SiC shape that requires the use of a sintering aid. In theory, the sintering aid forms a bond and bond between the SiC particles, and the bonding is substantially weaker than SiC-SiC bonding, such as direct bonding in the self-sintered shape.
[0136] The polymer-derived SiC of the present invention, especially the ultra-high purity SiC embodiments through vapor deposition processes, crystal growth, bonding processes and other processes, can be applied to applications such as broad band amplifiers, military communications, radars, telecommunications, data links, tactical data links, satellite communications, point-to-point radio powered electronic devices, LEDs, lasers, lighting, and sensors. In addition, the embodiment can be applied to transistors, such as high electron mobility transistors (HEMTs), including HEMT-based monolithic microwave integrated circuits (MMICs). The transistor can adopt a distributed (traveling wave) amplifier design method, and due to the larger band gap of SiC, it can achieve extremely wide bandwidth with a smaller footprint. Therefore, the embodiments of the present invention will include the above-mentioned devices and products made based on polymer-derived SiC.
[0137] The polymer derived SiC of the present invention, especially the ultra-high purity SiC embodiments obtained through vapor deposition processes, crystal growth, bonding processes and other processes, can also be used in brake rotors and their assemblies, brake disks and brake pads, and can also be used in the manufacture of precious and semiprecious stones, jewelry, moissanite, and cutting and grinding applications. Therefore, embodiments of the present invention will include the above-mentioned devices and articles made based on polymer derived SiC.
[0138] The polymer derived SiC of the present invention, especially the ultra-high purity SiC embodiment, can be combined with other ceramic powder formulations to provide greater benefits and reduce costs for the preparation process of the ceramic powder, for example, BN / SiC / ZrO 2 The composition is mixed with other refractory / engineering ceramic powders, such as AlN, BC, BN, Al 2 O 3 、ZrO 2 , C, SiC, WC and SiN. Therefore, embodiments of the present invention will include the above-mentioned devices and articles made based on polymer-derived SiC.
[0139] These embodiments of the present invention can also be applied to metal alloys, such as for preparing cermets, or other metallurgical mixtures and alloys, which can be combined with Ti, Fe, Ni and Co. Therefore, it can be used to prepare polymer-derived SiC-Ti alloys, and polymer-derived SiC-Co alloys.
[0140] The polymer derived SiC ceramic powder formulation embodiments of the present invention can be applied to the composition or construction of the following articles: kiln furniture, furnace tubes, furnace belt links, roller furnaces, nozzles, bearings, corrosion resistant seals, crucibles, refractory materials, thermal protection systems, ramjet engines (RAM-Jet) / supersonic combustion ramjet engines (SCRAM-Jet), rockets, space shuttles, rocket nose cones or any objects flying at speeds exceeding Mach 3, leading edge impact protection systems, SiC / SiC reinforced composites, SiC / C reinforced composites, DC magnetron sputtering targets, thermocouple covers, pump wheel seals, and valve sleeves.
[0141] The polymer-derived SiC, SiOC, and particularly the ultra-high purity SiC and SiOC embodiments of the present invention, which are obtained by vapor deposition processes, crystal growth, bonding processes, and other processes, can be applied to multilayer structures, such as layers on a substrate. The layers can be crystalline, single crystal, polycrystalline, or amorphous. Some structures have multiple different layers, such as a substrate layer, a tie layer, a SiC layer, a SiOC layer, and other materials. In one embodiment, sapphire can be used as a substrate for epitaxial SiC layers. GaN can also be used as a substrate. The tie layer can be used to adjust the lattice mismatch between different crystal lattice parameters. Therefore, when SiOC is used as a substrate, it can support the growth of SiC or GaN layers through the tie layer.
[0142] In one embodiment of the process, high purity, polymer derived SiC, and preferably very small particle size (e.g., less than about 100 μm, less than about 10 μm), having a purity of about 99.999%, preferably 99.9999%, more preferably 99.99999%, can be sintered into optical components. The optical components can transmit selected wavelengths, such as 360 to 800 nm, have a refractive index of about 2.65 in visible light, have excellent optical properties and are free of aberrations, occlusions and other optical defects, and are very tough (e.g., chemical resistance, wear resistance, temperature resistance of SiC). Therefore, it can provide significant improvements for windows or other transparent components, such as mobile phone screens, tablet screens, touch screens, etc. It is also used in the body of these components, and polymer derived SiC windows are particularly advantageous in their applications, such as in harsh environments. It can also be used in many optical applications, including: light generation, such as lasers, laser diodes or other light sources; light shaping and transmission, such as optical fibers, windows, prisms, lenses or other optical devices, mirrors, internal reflection elements (such as prisms and optical modules that rely on internal reflection to guide light). In addition to ultraviolet, visible and IR light, SiC optical components can be used in applications with electromagnetic radiation wavelengths, such as microwaves, millimeter waves, X-rays, and high-energy beams.
[0143] The polysilicon carbide derived SiC of the present invention, especially the high purity SiC embodiment, has many properties that make it advantageous in the fields and applications of electronics, solar energy, and energy transfer. It can be used as a stable semiconductor material and is suitable for some demanding applications, including applications in high energy, high frequency, high temperature and corrosive environments. Polymer-derived SiC is a very hard material with a Young's modulus of 424GPa. It is essentially inert chemically and does not react with any material at room temperature.
[0144] Furthermore, prior to the present invention, the addition of the desired dopant to a material such as silicon carbide by diffusion was not feasible from all practical standpoints, and the dopant can be added in the form of a precursor, which allows it to be controlled and grown in a pear-shaped crystal or other material structure. The precursor formulation embodiments of the present invention include adding the dopant or a composite carrying or combining the dopant to the ceramic by vapor deposition, and the resulting SiC.
[0145] In addition, the addition of dopants or other additives provides custom or predetermined properties to the wafer, as well as the layers and structures produced from the polymer-derived SiC and SiOC embodiments of the present invention, which can be used in conjunction with the polymer-derived materials of the present invention, or as part of the polymer-derived materials of the present invention. In this embodiment, the additive that can enhance the properties is not considered an impurity because it must be present in the final product according to the intention. The additive that can enhance the properties can be incorporated into the liquid precursor material. Depending on the nature of the additive, it can be used as a precursor backbone, as a composite or part of a composite, or in other forms that can persist (for example, in a form that allows the additive to perform its function in the final product). The additive that can enhance the properties can also be used as a coating of the SiC or SiOC powder material, a vapor or gas during processing, or as a powdered form mixed with polymer-derived SiC or SiOC particles. In addition, the form and manner of the additive that can enhance the properties should preferably have minimal adverse effects on the processing conditions, time and quality of the final product, and more preferably no adverse effects. Thus, polysilicon oxide carbide derived SiC having a purity greater than 5 nines, greater than 6 nines, and greater than 7 nines, has a large amount of property enhancing additives present in an amount of about 0.01% to about 50%, about 0.1% to about 5%, about 1% to 10%, less than 25%, less than 20%, less than 10%, less than 1%, or more / less depending on the desired property that the additive is intended to impart.
[0146] Silicon carbide is generally not in a liquid state, and it sublimes directly in a vacuum at a temperature above 1,800°C. FIG. 10 provides a partial pressure curve of SiC. Generally, in industrial and commercial applications, reaction conditions are established based on the sublimation being carried out at a temperature of about 2,500°C or higher. During the sublimation process, silicon carbide generally forms a composition of Si, SiC and SiC 2 Typically, temperature determines the ratio of the different components in the silicon carbide vapor. However, the present invention provides the ability to preselect and control these components in the silicon carbide vapor, such as by controlling the amount of excess carbon present in the polysilicon oxycarbide. In addition, under controlled circumstances, by varying the porosity of the polysilicon oxycarbide derived SiC, the amount of excess carbon present, and both (when used as a starting material for a vapor deposition process), such as having a layer of SiC material with different predetermined amounts of excess carbon, the composition of the SiC vapor can be controllably varied, and varied by controlling time.
[0147] Polysilicon oxycarbide derived SiC, and SiC pear-shaped crystals, wafers and other structures prepared therefrom, exhibit polymorphism and a single-dimensional polymorphism known as polytypism. Thus, polysilicon oxycarbide derived SiC can exist in a theoretically infinite number of different polytypes. As used herein, unless otherwise specified, "polymorphism," "polytype," and other similar terms shall have the broadest possible meaning, including tetrahedral SiC (SiC 4 ) can be configured into a variety of different frameworks, structures or arrangements. These polytypes are divided into two categories: α and β.
[0148] The α-class embodiments of SiC derived from polysilicon oxycarbide in the present invention generally include hexagonal (H), rhombohedral (R), trigonal (T) structures and combinations thereof. Its β-class includes cubic (C) or zinc blende structures. Thus, for example, polytypes of silicon carbide derived from polysilicon oxycarbide include: 3C-SiC (β-SiC or β3C-SiC), with a stacking sequence of ABCABC; 2H-SiC, with a stacking sequence of ABAB; 4H-SiC, with a stacking sequence of ABCBABCB; and 6H-SiC (a common structure of α-class silicon carbide, α6H-SiC), with a stacking sequence of ABCACBABCACB. α-class silicon carbide also includes 8H, 10H, 16H1, 8H, 19H, 15R, 21R, 24H, 33R, 39R, 27R, 48H and 51R.
[0149] The polysilicon oxycarbide derived SiC in the embodiments of the present invention may be polycrystalline or monocrystalline. Generally speaking, polycrystalline materials have grain boundaries as the contact surface between two grains, or crystallites of the material. The grain boundaries may be between polymorphs of the same type with multiple orientations, between polymorphs of different types with one or multiple orientations, or different combinations of the two. Monocrystalline structures consist of a single polymorph and are substantially free of grain boundaries.
[0150] Embodiments of the present invention provide the ability to meet the demand for high purity silicon carbide, particularly high purity single crystal carbide material for use in end products such as semiconductors. Thus, for end products and applications requiring high purity materials, there is a need for low cost silicon carbide raw materials having a purity of at least about 99.9%, at least about 99.99%, at least about 99.999%, at least about 99.9999%, and at least about 99.99999% or higher.
[0151] High-purity single-crystal silicon carbide material has many favorable properties and characteristics. For example, it has a Young's modulus of 424 GPa and is very hard. Polycrystalline silicon carbide is also very hard, depending on its particle structure and other factors.
[0152] Embodiments of polysilicon oxycarbide derived SiC of the present invention include seeds, pear-shaped crystals, and other structures that provide larger diameters (e.g., about 5 inches, greater than 5 inches, about 6 inches, greater than 7 inches, about 8 inches, greater than 8 inches, about 9 inches, greater than 9 inches, about 12 inches, and greater) or cross-sections. The purity of the structures having larger diameters or cross-sections is preferably at least about 99.9%, at least about 99.99%, at least about 99.999%, at least 99.9999%, and at least 99.99999% or greater.
[0153] Embodiments of the present invention include articles, such as semiconductors, having silicon carbide band gaps that vary depending on the polytype, from 2.39 eV for 3C-SiC (beta-SiC) to 3.33 eV for 2H-SiC. The band gap for 4H-SiC is 3.265 eV, and the band gap for alpha silicon carbide (6H-SiC) is 3.023. These band gaps are greater than the 1.11 eV band gap of Si. These high band gaps allow silicon carbide materials to be used in sensors, such as gas sensors that operate at high temperatures (e.g., up to 1,000°C). The response time of silicon carbide-based gas sensors at temperatures of about 1,000°C is only a few milliseconds.
[0154] The polymer-derived SiC and SiOC in the embodiments of the present invention, and in particular the high-purity polymer-derived SiC and SiOC, can be used in power devices and their applications. For power device applications, the breakdown electric field strength E max E is an important property. This property quantifies the maximum electric field strength reached before material breakdown (e.g. catastrophic breakdown) occurs. max It depends on the doping degree of the material. For SiC and Si materials with the same doping degree, the E of SiC material is max Compared with Si material max 4-10 times larger. max and relative E maxIt can also be viewed from the perspective of the relative strength of devices with the same blocking voltage. Thus, a Si device with a 1KV blocking voltage will have a critical field strength of about 0.2MV / cm, while a similar SiC device will have a critical field strength of about 2.49MV / cm.
[0155] The polymer-derived SiC, SiOC, and especially the high-purity polymer-derived SiC and SiOC materials in the embodiments of the present invention can be used in high-frequency devices and high-frequency applications. The saturation drift velocity is an important property of high-frequency devices. The saturation drift velocity of silicon carbide is 2x10 7 cm / sec 2 , while the saturation drift velocity of similar silicon is only half of the former. High saturation drift velocity is advantageous for high-gain solid devices. Because the embodiments of the present invention provide high-purity, low-cost silicon carbide, the use of silicon carbide can become a preferred choice of material for manufacturing the above-mentioned devices. The existing technology before the present invention would not make this choice because the cost and difficulty of using silicon carbide are too high, and the required purity cannot be obtained.
[0156] In the embodiments of the present invention, polymer-derived SiC, SiOC, and especially high-purity polymer-derived SiC and SiOC can be used in high thermal conductivity applications. At room temperature, the thermal conductivity of silicon carbide is higher than that of copper and most other metals. For example, at room temperature, the thermal conductivity of silver is 4.18 W / (cm·K) and that of copper is 4.0 W / (cm·K). At room temperature, the thermal conductivity of high-purity silicon carbide is higher than about 4.0 W / (cm·K), greater than about 4.5 W / (cm·K), about 4.9 W / (cm·K) or higher.
[0157] The embodiments of the present invention and the improvements in SiC processing and materials provided by the embodiments can replace silicon materials in most electronic applications, and additionally provide new applications and uses beyond conventional silicon-based semiconductors and electronic applications.
[0158] The polysilicon oxycarbide derived high purity SiC in the embodiments of the present invention, such as polysilicon oxycarbide derived SiC having a purity of at least about 99.9%, at least about 99.99%, at least about 99.999%, at least about 99.9999%, at least about 99.99999% or more, can have many different polytypes. The polymer derived high purity SiC and SiOC can exist in the form of α, β, and combinations and variations thereof. The α class of the polysilicon oxycarbide derived high purity SiC in the embodiments of the present invention generally includes hexagonal (H), rhombohedral (R), trigonal (T) structures and different combinations thereof. The β class of the polysilicon oxycarbide derived high purity SiC generally includes cubic (C) or sphalerite structures. Thus, for example, polymorphs of high-purity silicon carbide derived from polysilicon oxycarbide include: 3C-SiC (β-SiC or β3C-SiC); 2H-SiC; 4H-SiC; and 6H-SiC (a common structure of α-type silicon carbide, α6H-SiC), with a stacking sequence of ABCACBABCACB. Other α-type silicon carbides include, for example: 8H, 10H, 16H, 18H, 19H, 15R, 21R, 24H, 33R, 39R, 27R, 48H, and 51R. The high-purity SiC derived from polysilicon oxycarbide in the embodiments of the present invention may be polycrystalline or single crystal. High-purity SiOC, and SiC derived from SiOC may be amorphous.
[0159] Embodiments of the present invention have the ability to provide high purity SiOC and SiOC in the form of volumetric structures, such as small columns, coal balls, bricks, tablets, pills, sheets, discs, cubes, spheres, rods, random shapes, etc. The above volumetric shapes have a large range of sizes, typically from about 1 / 16 cubic inch to about 1 cubic inch, but may also be larger or smaller. The volumetric structures in embodiments of the present invention can be very soft and brittle, or fragile, and preferably break under average hand pressure. Therefore, these fragile SiC volumetric structures can have: elastic modulus below about 200 GPa, below about 150 GPa, below about 75 GPa, below about 10 GPa and lower; below about 1,400 Kg / mm 2 , less than about 800 Kg / mm 2 , less than about 400Kg / mm 2 , less than about 100Kg / mm 2 and lower hardness; and, less than about 1,850 MPa, less than about 1,000 MPa, less than about 750 MPa, less than about 200 MPa, less than about 50 MPa, and lower compressive strength. Thus, these brittle SiC bulk shapes are substantially weaker than their SiC constituent materials, which are reported to have an elastic modulus of about 410 GPa, a tensile strength of about 2,800 Kg / mm 2The SiC material has a hardness of about 1000 MPa and a compressive strength of about 3,900 MPa. The actual density of the SiC material measured by Helium Pycnometry is about 3.0 to 3.5 g / cc, about 3.1 to 3.4 g / cc, or about 3.2 to 3.3 g / cc. The apparent density (or specific gravity) of SiC fragile volume shapes (such as small pillars, pills, etc.) is significantly lower than its actual density.
[0160] The SiC mass (e.g., bulk shape of granular SiC particles, brittle mass) preferably, and usually, has an apparent density significantly lower than its actual density (the actual density of SiC particles is about 3.1 to 3.3 g / cc). Generally speaking, the apparent density of the granular SiC obtained by crushing the brittle mass is substantially the same as the actual density. The apparent density of the brittle mass (e.g., puck-shaped, small columnar, disc-shaped, or sheet-shaped) may be less than about 3 g / cc, less than about 2 g / cc, less than about 1 g / cc, or less, and may be about 0.5 to about 1.5 g / cc, or about 0.4 to about 2 g / cc. The bulk density of the SiC particles may be less than about 3.0 g / cc, less than about 2.0 g / cc, or less than about 1 g / cc, and may be about 0.1 to about 2 g / cc, or about 0.5 to about 1.5 g / cc. Higher or lower apparent and bulk densities are also contemplated. Furthermore, a specific (i.e., predetermined and precise) apparent density of polymer-derived SiC can be provided to match, and preferably improve, and more preferably optimize subsequent manufacturing processes. For example, in the manufacture of CVD wafers, a friable mass of SiC particles can have an apparent density specifically designed and adjusted to match the CVD device. In this way, each CVD device in a facility can have a customized feedstock, which optimizes the performance of each device by using feedstock (e.g., SiC friable mass) with a predetermined and precise apparent density.
[0161] The brittle SiC bulk shape can thus be easily and quickly broken down into numerous smaller SiC particles having the strength characteristics typical of SiC. The diameters of these smaller particles can be less than about 10 mm, less than about 1 mm, less than about 0.01 mm, less than about 100 μm, less than about 10 μm, and less than about 1 μm, less than about 500 nm, to less than about 100 nm, with larger or smaller particle sizes also being contemplated.
[0162] Thus, embodiments of the present invention provide the preparation of a SiC brittle mass or bulk shape produced from a SiOC precursor, and granular SiC obtained from the SiC brittle mass. The strength of the granular SiC is significantly stronger than the bulk properties of the SiC brittle mass. For example, the elastic modulus of the granular SiC may be about 2, 3, 4 times, and more than that of the SiC brittle mass; the hardness of the granular SiC may be about 2, 3, 4 times, and more than that of the SiC brittle mass; the compressive strength of the granular SiC may be about 2, 3, 4 times, and more than that of the SiC brittle mass; and combinations and variations of the above-mentioned enhanced properties.
[0163] This is done by, for example Figure 1 The SiC friable mass obtained in the embodiment process (e.g., 103c of section 108) can be decomposed into granular SiC by a crushing device, such as a ball mill, an attritor, a rotor-stator mill, a hammer mill, a jet mill, a drum mill, a glass bead mill, a media mill, a grinder, a high-speed mixer (homogenizer), a two-plate mill, a powder water mixer (dough mixer) and other types of grinding, milling and processing equipment.
[0164] The SiC brittle mass has internal pores. The pores are preferably open holes, or substantially open pores. In this way, the brittle mass typically provides a substantially larger available surface area than granular SiC because the granular SiC is pressed against each other. Therefore, for example, if a brittle SiC disc is used to prepare SiC pear-shaped crystals (for subsequent conversion into SiC wafers) during a vapor deposition process, relative to the use of granular SiC, the brittle SiC disc will provide a substantially larger surface area for generating SiC vapor, and provide a substantially longer path for the movement of SiC vapor. In theory, the increase in surface area and path provides the ability to improve the growth rate and quality of SiC pear-shaped crystals (as well as the quality of the wafers prepared subsequently). The brittle SiC disc, such as a SiC mass, is easier to transport, measure and use relative to granular SiC materials.
[0165] The SiC friable mass preferably and typically has a lower apparent density relative to its actual density (eg, 3.2 g / cc). Typically, the granular SiC obtained by crushing the friable mass has substantially the same apparent density and actual density, eg, about 3.1 to 3.3 g / cc.
[0166] Compared to the forces required for conventional SiC preparation methods (e.g., carbon thermal reduction of silica based on the Acheson method), the forces required to break the SiC friable mass into a granular form are minimized. Conventional methods typically produce a whole block of SiC in batches, which must then be granulated, such as grinding, cutting, trimming, or grinding to a usable size. Therefore, embodiments of the present invention avoid the use of such heavy or rough grinding equipment to granulate the whole block of SiC, and further avoid the high costs, such as electricity, generated by operating the above-mentioned grinding equipment. Embodiments of the present invention also greatly reduce the time required to granulate SiC. Using the above-mentioned heavy grinding equipment to granulate the whole block of SiC to a usable size can take several weeks, while the granulation of the SiC friable mass in the embodiments of the present invention only takes several hours, 1 hour, less than 1 hour, less than 30 minutes, several minutes, and less. The grinding process can, for example, be used as a post-processing processing stage.
[0167] The characteristics of high purity polysilicon oxide carbide derived SiC provide a number of advantages and benefits for its use, for example, as a source or starting material for Si and C, and in vapor deposition processes, systems and apparatus, and other techniques for producing or growing SiC masses, structures, articles or volumetric shapes. These characteristics include: the ability to have high purity levels; the ability to control particle size distribution (shape and / or size); the ability to have a volumetric shape; a predetermined volumetric shape (e.g., puck, pill, disk, etc.); the ability to have, control porosity; predetermined porosity; the ability to control carbon amount; predetermined carbon amount (excess carbon, i.e., carbon in excess of the stoichiometric amount, and deficient carbon, i.e., carbon in less than the stoichiometric amount); and combinations and variations of the above characteristics and other properties. Currently or foreseeably, the present invention also provides additional benefits, for example, benefits in the vapor deposition process include: shortened growth time of pear-shaped crystals or other structures; longer operating time before cleaning; the ability to optimize the equipment; the ability to grow pear-shaped crystals or other structures with larger diameters; the ability to improve quality; reducing the occurrence, surface and area of problems in pear-shaped crystals or other structures (such as blockage and defects of microtubes); reducing costs; greater control over the process; and different combinations and variations of the above.
[0168] It should be understood that the use of titles in the present specification is intended to explain the purpose of the present invention, rather than to limit the scope of the present invention in any form. Therefore, the processes and disclosures under the titles should be read in conjunction with the present specification, which includes a number of different examples. The use of titles in this specification does not limit the scope of protection of the present invention.
[0169] Typical polymer-derived ceramic precursor formulations, and in particular polysilicon carbide precursor formulations, can generally be prepared by three types of processes, and other processes, as well as different combinations and variations thereof, may also be used. These processes generally involve combining precursors to form a precursor formulation. One type of process generally involves mixing the precursor materials with each other, preferably by a solvent-free process, in which no chemical reaction occurs, such as a "mixing type process". Another type of process generally involves chemical reactions, such as by a "reaction type process" to produce a specific (e.g., customized) precursor formulation, which can be monomers, dimers, trimers, and polymers. The third type of process involves chemical reactions of two or more components in a solvent-free environment, such as a "reaction mixing type process". Typically, in the mixing process, substantially and preferably, all chemical reactions occur in subsequent processing, such as in curing or / and pyrolysis.
[0170] It should be understood that the use of the terms "mixing process", "reaction process" and "reaction mixing process" as shorthand references is for convenience of presentation. These terms are not, and should not be considered, limiting. For example, a reaction process may be used to produce a precursor material that is subsequently mixed with another precursor material.
[0171] In the present specification, these process types are described under the corresponding headings. It is understood that the teachings for one process under one heading are mutually applicable to the teachings for another process under another heading, and are also mutually applicable to other content parts, embodiments and teachings in the present specification, and vice versa. The starting or precursor materials of one type of process can be used in other types of processes. In addition, it is understood that the processes described under the headings should be read in conjunction with the full text of the present specification, which includes a number of different examples and embodiments.
[0172] Curing and pyrolysis of preferred SiOC-derived SiC
[0173] Preferably, in the process of preparing SiC and the material for preparing SiC, the polysilicon oxycarbide precursor is mixed in clean air at 1 atmosphere.
[0174] Preferably, in the process of preparing SiC and the materials for preparing SiC, the curing is carried out in a temperature range of about 20°C to about 150°C, about 75°C to about 125°C, and about 80°C to about 90°C. The curing is carried out for a period of time to preferably produce a hard solidified material. The curing can be carried out in air or an inert atmosphere, and is preferably carried out in an argon atmosphere at ambient pressure. Most preferably, in order to obtain high-purity materials, the furnace, container, operating equipment and other components in the curing device are clean, and they are substantially free of and do not give any elements or materials that are considered as impurities or contaminants to the obtained solidified material.
[0175] Preferably, in the process of preparing SiC and materials for preparing SiC, pyrolysis is carried out in a temperature range of about 800°C to about 1300°C, 900°C to about 1200°C, and 950°C to about 1150°C. The pyrolysis is carried out for a period of time to preferably completely pyrolyze the preform. Preferably, the pyrolysis is carried out in an inert gas, such as argon, and more preferably in flowing argon at (or about) atmospheric pressure. The flow rate of the argon is about 1,200cc / min to about 200cc / min, 800cc / min to about 400cc / min, and 500cc / min. Preferably, an initial vacuum evacuation is performed on the processing furnace to reduce its pressure to at least less than 1E-3Torr, and then it is re-pressurized with an inert gas (such as argon) to more than 100Torr. More preferably, the pressure after the vacuum evacuation is completed is less than 1E-5Torr before re-pressurizing with an inert gas. Before the next step, the vacuum extraction process can be performed 0 to more than 4 times. Most preferably, in order to obtain high-purity materials, the furnace, container, operating equipment and other components in the solidification device are clean, and they do not substantially contain and do not give any elements or materials that are considered as impurities or contaminants to the obtained solidified material.
[0176] In embodiments where low levels of N and O are desired, a depressurization operation to 10E-6 Torr and re-pressurization with an inert gas is performed using a vacuum, preferably a turbo pump. This purging process can be performed one or more times to achieve lower levels of N and O. A "purge" gas can help purge the furnace as volatiles are generated.
[0177] Preferably, in the process of preparing SiC, the ceramic SiOC is converted to SiC in a subsequent or subsequent pyrolysis or conversion step. The conversion step may be part of the pyrolysis of the SiOC preform (e.g., immediately following the pyrolysis), or may be a completely separate step that is different in time and / or location. Depending on the type of SiC desired to be obtained, the conversion step may be carried out at about 1,200°C to about 2,550°C, and about 1,300°C to about 1,700°C. Typically, at temperatures of about 1,600°C to 1,900°C, the conversion step tends to produce β-type SiC as time increases. At temperatures above 1,900°C, the conversion step tends to produce α-type SiC as time increases. Preferably, the conversion is carried out in an inert gas, such as argon, and more preferably in flowing argon at (or about) atmospheric pressure. The flow rate of the argon gas is about 600cc / min to about 10cc / min, about 300cc / min to about 50cc / min, and about 80cc / min to about 40cc / min. Most preferably, in order to obtain high purity materials, the furnace, container, operating equipment and other components in the solidification device are clean and substantially free of and do not contribute any elements or materials that are considered impurities or contaminants to the obtained SiC.
[0178] The yield of subsequent SiOC-derived SiC is typically about 10% to 50%, typically about 30% to 40%, but may be higher or lower.
[0179] Most preferably, in the process of preparing high purity SiC, the activities associated with material preparation, curing, pyrolysis and conversion are performed in a clean room or under clean room conditions, such as clean room conditions of at least ISO 5, ISO 4, ISO 3, ISO 2 and ISO 1 under the ISO 14644-1 clean room standard. In one embodiment of the present invention, the material transportation step is performed in a clean room of at least ISO 5, while the pyrolysis and conversion steps are performed under lower clean level conditions (ISO>5).
[0180] The use of ultra-high purity polymer-derived SiC in vapor deposition techniques provides superior quality, reduced defects in pears, wafers, and semiconductors compared to pears, wafers, and semiconductors produced from other SiC sources (i.e., non-polymer-derived ceramic-based SiC). Without being limited by existing theory, the polymer-derived ceramic process used to obtain ultra-high purity SiC from a liquid SiOC starting material (e.g., a polysilicon oxycarbide precursor) provides a starting raw material with different characteristics and morphology than other SiC sources, and these differences allow the polymer-derived ceramic material to form a preform significantly better than other SiC sources. When polymer-derived ceramic SiC is used as a seed, the quality and manufacturing efficiency of the resulting pears and wafers will be additionally improved compared to other SiC seeds. These improvements include improvements in at least the following properties and characteristics, and / or the following undesirable properties or effects:
[0181] Bow: A measure of the concave or convex deformation of the center of the wafer surface that is independent of any thickness variation. Bow is determined by the wafer center point referenced to a reference plane defined by three equidistant points on a circle of 6.35 mm diameter (less than the wafer diameter). Bow is a bulk property of the wafer, not of the exposed surface. Bow is usually determined when the wafer is in a free, unclamped state (not to be confused with warp, below).
[0182] Diameter: The straight-line distance across a circular silicon wafer that passes through the center of the wafer and does not pass through any flat or other peripheral reference areas.
[0183] Edge contour: The cross-sectional edge of a wafer that has been ground or etched to shape the edge. The edge may be rounded or beveled.
[0184] Flatness: For the wafer surface, the front surface deviation expressed as TIR or maximum FPD, which is relative to a specific reference surface when the wafer back surface is completely flat (that is, it can be completely adsorbed on an ideal flat chuck by vacuum). The flatness of the wafer can be described as: overall flatness; the maximum value of the local flatness measured at all sites; or the percentage of sites with a local flatness equal to or less than a specific value.
[0185] Flatness quality area: The portion of the wafer surface suitable for a specific flatness. The flatness quality area is most often defined by the edge exclusion area, which is a peripheral annular region with a width of typically 3 mm.
[0186] Focal plane: The plane perpendicular to the optical axis of the imaging system and containing the focal point of the imaging system.
[0187] Focal plane deviation (FPD): The distance from a point on the wafer surface to the focal plane, parallel to the optical axis.
[0188] Global flatness: TIR or maximum FPD within the flatness quality zone relative to a specific reference surface.
[0189] Maximum FPD: The maximum absolute value of focal plane deviation.
[0190] Primary flat: The plane of maximum length oriented to a particular crystallographic plane, also called the principal plane.
[0191] Reference plane: A plane defined by one of the following: three points located at specific locations on the front surface of the wafer; a least squares fit plane fitted to all points in the good flatness zone relative to the front surface of the wafer; a least squares fit plane fitted to all points in a certain area relative to the front surface of the wafer; or an ideal back surface (same as the ideal planar chuck surface in contact with the wafer as described above).
[0192] Secondary flat(s): One or more planes shorter than the primary plane, whose angular position relative to the primary plane determines their conductivity type and wafer orientation. Secondary planes are also called facets.
[0193] Site: A rectangular area on the front surface of the wafer whose sides are parallel and perpendicular to the main plane and whose center falls within the flatness quality zone.
[0194] Site flatness: The TIR or maximum FPD of a certain site that falls within the high-quality flatness zone.
[0195] Thickness: The distance through the wafer between corresponding points on the front and back surfaces.
[0196] Total indicator reading (TIR): The shortest perpendicular distance between two planes that are parallel to a reference plane that contains all points within a specific flatness quality area or front surface portion of the wafer.
[0197] Total thickness variation (TTV): The difference between the maximum and minimum thickness of a wafer measured in a thickness scan or a series of points.
[0198] Warp: The difference between the maximum and minimum distances between the center plane of the wafer being measured and a reference plane during a thickness scan. Warp is a bulk property of the wafer, not a property of the exposed surface. The center plane of the wafer may contain areas with upward and / or downward curvature. Typically, warp is determined when the wafer is in a free, unclamped state (not to be confused with bow above).
[0199] Auto-doping: The intentional addition of dopants into a vapor phase that is incorporated into the epitaxial layer during growth.
[0200] Auto-doping barrier: A film or layer that blocks the transport of impurity atoms from the back surface of the substrate to the epitaxial layer during epitaxial deposition. This barrier is also called a backseal.
[0201] Conductivity type: It defines the nature of most charge carriers in silicon: n-type material, whose main charge carriers are electrons, which are created when donor dopant impurities are added to silicon; p-type material, whose main charge carriers are holes, which are created when acceptor dopant impurities are added to silicon.
[0202] Crystal orientation: The crystal axis along which silicon grows.
[0203] Dislocation: A line defect in a crystal that forms a grain boundary between slip and non-slip regions.
[0204] Dislocation density: the number of dislocation pits per unit area on the exposed crystal surface.
[0205] Dislocation etch pit: A well-defined depression near a stressed or defective crystal lattice.
[0206] Dopant: A chemical element from the 3rd (e.g., boron) or 5th (e.g., phosphorus or antimony) column of the periodic table that is intentionally added to silicon crystals in trace amounts to establish conductivity type and resistivity. P-type / boron / 0.001-50ohm·cm. N-type / phosphorus / 0.1-40ohm·mcm, antimony / 0.005-0.025ohm·cm, arsenic / <0.005ohm·cm.
[0207] Extrinsic gettering: The introduction of controlled damage or stress into the lattice structure by mechanical means or by the deposition of polysilicon or other thin films on the back surface of a silicon wafer.
[0208] Flat orientation: A crystal plane that happens to be exactly the same as the principal plane surface, which is usually <110> flat.
[0209] Miller indices: The reciprocal of the edges of a crystal face on the x, y, and z axes. For example, the face of a cube perpendicular to the x axis is <100> Planes. Families of planes are indicated by curly brackets; for example, all cube faces are {100} planes. Directions are indicated by Miller indices in square brackets; for example, the x-axis is the
[100] direction and the cube diagonals are the
[111] directions. Families of directions are indicated by angle brackets; for example, all cube axes are <100> Direction. A negative direction is indicated by a minus sign in the index position; for example, the negative x-axis is in the <-100> direction.
[0210] Polycrystalline silicon (polysilicon): A crystal composed of silicon with random orientation and high-angle grain boundaries and / or twin boundaries.
[0211] Radial oxygen variation: The difference between the average oxygen concentration at one or more symmetrically distributed points on the wafer and the oxygen concentration at the center of the wafer, expressed as a percentage of the central oxygen concentration. Unless otherwise specified, Siltec considers radial oxygen variation to be determined by the average oxygen concentration at two points 10 mm from the edge of the wafer. Radial oxygen variation is sometimes determined by the average oxygen concentration at symmetrical points located halfway between the center and the edge of the wafer. Radial oxygen variation is also called oxygen gradient.
[0212] Radial resistivity variation: The difference between the average resistivity at one or more symmetrically distributed points on the wafer and the resistivity at the center of the wafer, expressed as a percentage of the center resistivity. Unless otherwise specified, radial resistivity variation is considered to be determined by the average resistivity of 4 points on two perpendicular diameters of the wafer, 6 mm from the edge of the wafer. Radial resistivity variation is sometimes determined by the average resistivity of 4 symmetrical points located halfway between the center and the edge of the wafer. Radial oxygen variation is also called resistivity gradient.
[0213] Resistivity (ohm·cm): The ratio of the potential gradient parallel to the current flow to the current density. In silicon, the resistivity is controlled by adding dopants; adding more dopants results in lower resistivity.
[0214] Slip: A process of plastic deformation during which one part of the crystal is displaced in shear relative to another part, which does not affect the crystallinity of the silicon. After the preferred etching, slip is evidenced by a pattern of parallel straight lines of 10 or more dislocation pits per millimeter that do not necessarily touch each other. <111> On the surface, the straight lines are adjacent to each other at an angle of 60°; <100> On the surface, they meet at an angle of 90°.
[0215] Stacking fault: A surface defect in a crystal caused by a deviation from the normal atomic stacking order. Stacking faults can occur in a single crystal, during epitaxial deposition (usually caused by a contaminated or structurally defective substrate surface), or during oxidation. <111> On the surface, stacking faults can be visualized by etching with preferred closed or partial equilateral triangles.
[0216] Striations: Spiral features on the surface of silicon wafers associated with local variations in impurity concentration. These variations are attributed to periodic differences in dopant addition during the solid-liquid interface reversal during crystal growth. Striations are visible to the naked eye after optimal etching and appear continuous at 100x magnification.
[0217] Subsurface damage: Residual crystal defects that appear only after a preferred etch of the polished silicon surface. This damage is generally believed to be caused by mechanical handling of the wafer.
[0218] Twinned crystal: A crystal whose lattice consists of two parts that are related in orientation as mirror images across a continuous plane called the twin plane or twin boundary. In silicon, this plane is <111> Plane. Twinned crystals are also called twins.
[0219] Wafer orientation: The crystal plane described by the Miller indices that coincides exactly with the wafer surface. Typically, the wafer surface coincides with a low-index plane perpendicular to the growth axis by a few degrees. Thus, the wafer orientation can also be described by the angular deviation of the low-index crystal plane from the polished wafer surface.
[0220] Chip: An area formed by the removal of material from the surface or edge of a wafer. The size of a chip is defined by its maximum radial thickness and peripheral chord length measured through the orthographic projection of the sample profile. Chip is also known as clamshell, conchoidal fracture, edge chipping, flake, notch, peripheral chipping, peripheral serration, or surface chipping.
[0221] Contamination: In a broad sense, foreign matter visible to the naked eye on the surface of a wafer. In most cases, it can be removed by gas purge, cleaning with detergents, or chemical reactions. See also particle contamination and stain.
[0222] Rack: A cleavage that extends to the surface of the wafer and may or may not extend through the entire thickness of the wafer. A rack is also called a crack or fracture.
[0223] Cratering: A surface structure with irregular closed-loop ridges and a smooth central area.
[0224] Crow's-foot: <111> The cross cracks on the surface resemble "crow's claws".
[0225] Dimple: A smooth depression on the surface of a wafer with a diameter greater than 3 mm.
[0226] Fracture: A single or multiple linear cracks radiating from a point.
[0227] Groove: A shallow scratch with rounded edges, usually the remnant of a scratch that was not completely removed during the polishing process.
[0228] Haze: A cloudy or foggy appearance that can be caused by light scattering from microscopic surface irregularities such as depressions, bumps, small ridges or scratches, or particles.
[0229] Embedded Abrasive Grains: Abrasive grains that are mechanically incorporated into the surface of the silicon wafer. This type of contamination can occur during the slicing, grinding, or polishing process.
[0230] Indent: An edge defect extending from the front surface to the back surface of a silicon wafer.
[0231] Light point defects (LPD): Individual reflective spots that appear when a narrow beam of light is irradiated perpendicular to the surface of the chip.
[0232] Mound: An irregularly shaped projection with one or more faces. Mounds can be extensions of bulk material and / or various forms of contamination. A high density of mounds can also appear as fog.
[0233] Orange peel: Large areas of rough surface similar to orange peel that are visible to the naked eye under fluorescent light but usually not visible to the naked eye under narrow-beam illumination.
[0234] Particulate contamination: A form of contamination that includes particles, such as dust, lint, or other material that rests on or protrudes from the wafer surface. This contamination can usually be removed from the wafer surface by blowing clean nitrogen.
[0235] Pit: A depression in a surface with beveled sides that intersect the surface in a discernible manner (in contrast to the rounded sides of the pit).
[0236] Saw blade defect: After polishing, a visible rough area with a characteristic pattern of the saw blade. This defect is discernible before chemical polishing and is also called a knife mark.
[0237] Scratch: A shallow scratch or cut below the surface with an aspect ratio greater than 5:1. A scratch is 0.12 μm deep and is visible to the naked eye under both incandescent (narrow beam) and fluorescent lighting. A micro scratch is less than 0.12 μm deep and is not visible to the naked eye under fluorescent lighting.
[0238] Spike: A thin, tree-like protrusion or crystalline filament that usually occurs at the center of a recess in the surface of an epitaxial layer.
[0239] Stain: A type of soiling such as streaks, marks or spots containing foreign chemical compounds such as organic matter or salts.
[0240] Wafers with the following characteristics can be prepared from polymer-derived ultra-high purity SiC material.
[0241]
[0242]
[0243] This group includes single crystal silicon grown by Czochralski (Cz) and Floating zone (Fz) processes.
[0244] The following examples are used to illustrate various embodiments of the precursor formulations, processes, methods, devices, products, compositions and applications of the present invention. These examples are for illustrative purposes and should not be considered as limiting the scope of the present invention. The percentages used in the following examples, unless otherwise specified, refer to the weight percentage of the total batch, preform or structure.
[0245] Examples
[0246] Example 1
[0247] The polysilicon carbide formulation was prepared by a mixing method. The formulation was prepared by mixing 41% MHF and 59% TV at room temperature. The precursor formulation had 0.68 moles of hydride, 0.68 moles of vinyl and 1.37 moles of methyl. Each 100 g of the precursor formulation contained the following molar amounts and molar ratios of Si, C and O.
[0248] element Molar amount Molar ratio of the total in the "Molar Amount" column Si 1.37 25% C 2.74 50% O 1.37 25%
[0249] By calculation, SiOC derived from this formulation would contain a calculated 1.37 mol C after all CO removal, with 0% excess C.
[0250] Example 2
[0251] A polysilicon carbide formulation was prepared by a mixing method. The formulation was prepared by mixing 90% methyl terminated phenylethyl polysiloxane (containing 27% X) and 10% TV at room temperature. Per 100 g of the precursor formulation, 1.05 moles of hydride, 0.38 moles of vinyl, 0.26 moles of phenyl and 1.17 moles of methyl were contained. Per 100 g of the precursor formulation, the following molar amounts and molar ratios of Si, C and O were contained.
[0252] element Molar amount Molar ratio of the total in the "Molar Amount" column Si 1.17 20% C 3.47 60% O 1.17 20%
[0253] By calculation, SiOC derived from this formulation would contain a calculated 2.31 mol C after all CO removal, with 98% excess C.
[0254] Example 3
[0255] A polysilicon carbide formulation was prepared by a mixing method. The formulation was prepared by mixing 70% methyl-terminated phenylethyl polysiloxane (containing 14% X) and 30% TV at room temperature. The precursor formulation contained 0.93 moles of hydride, 0.48 moles of vinyl, 0.13 moles of phenyl and 1.28 moles of methyl. The following molar amounts and molar ratios of Si, C and O were contained per 100 g of the precursor formulation.
[0256] element Molar amount Molar ratio of the total in the "Molar Amount" column Si 1.28 23% C 3.05 54% O 1.28 23%
[0257] By calculation, SiOC derived from this formulation would contain a calculated 1.77 mol C after all CO removal, with an excess of 38%.
[0258] Example 4
[0259] A polysilicon carbide formulation was prepared by a mixing method. The formulation was prepared by mixing 50% methyl-terminated phenylethyl polysiloxane (containing 20% X) and 50% TV at room temperature. The precursor formulation contained 0.67 moles of hydride, 0.68 moles of vinyl, 0.10 moles of phenyl and 1.25 moles of methyl. Each 100 g of the precursor formulation contained the following molar amounts and molar ratios of Si, C and O.
[0260] element Molar amount Molar ratio of the total in the "Molar Amount" column Si 1.25 22% C 3.18 56% O 1.25 22%
[0261] By calculation, SiOC derived from this formulation would contain a calculated 1.93 mol C after all CO removal, with an excess of 55%.
[0262] Example 5
[0263] A polysilicon carbide formulation was prepared by a mixing method. The formulation was prepared by mixing 65% methyl-terminated phenylethyl polysiloxane (containing 40% X) and 35% TV at room temperature. The precursor formulation contained 0.65 moles of hydride, 0.66 moles of vinyl, 0.25 moles of phenyl and 1.06 moles of methyl. Each 100 g of the precursor formulation contained the following molar amounts and molar ratios of Si, C and O.
[0264] element Molar amount Molar ratio of the total in the "Molar Amount" column Si 1.06 18% C 3.87 54% O 1.06 28%
[0265] By calculation, SiOC derived from this formulation would contain a calculated 2.81 mol C after all CO removal, with an excess of 166%.
[0266] Example 6
[0267] The polysilicon carbide formulation was prepared by a mixing method. The formulation was prepared by mixing 65% MHF and 35% dicyclopentadiene (DCPD) at room temperature. The precursor formulation contained 1.08 moles of hydride, 0.53 moles of vinyl, 0.0 moles of phenyl and 1.08 moles of methyl. Each 100 g of the precursor formulation contained the following molar amounts and molar ratios of Si, C and O.
[0268] element Molar amount Molar ratio of the total in the "Molar Amount" column Si 1.08 18% C 3.73 64% O 1.08 18%
[0269] By calculation, SiOC derived from this formulation would contain a calculated 2.65 mol C after all CO removal, with an excess of 144%.
[0270] Example 7
[0271] The polysilicon carbide formulation was prepared by a mixing method. The formulation was prepared by mixing 82% MHF and 18% dicyclopentadiene (DCPD) at room temperature. The precursor formulation contained 1.37 moles of hydride, 0.27 moles of vinyl, 0.0 moles of phenyl and 1.37 moles of methyl. Each 100 g of the precursor formulation contained the following molar amounts and molar ratios of Si, C and O.
[0272] element Molar amount Molar ratio of the total in the "Molar Amount" column Si 1.37 25% C 2.73 50% O 1.37 25%
[0273] By calculation, SiOC derived from this formulation would contain a calculated 1.37 mol C after all CO removal, with 0% excess C.
[0274] Example 8
[0275] The polysilicon carbide formulation was prepared by a mixing method. The formulation was prepared by mixing 46% MHF, 34% TV and 20% VT at room temperature. The precursor formulation contained 0.77 moles of hydride, 0.40 moles of vinyl, 0.0 moles of phenyl and 1.43 moles of methyl. The precursor formulation contained the following molar amounts and molar ratios of Si, C and O per 100 g.
[0276] element Molar amount Molar ratio of the total in the "Molar Amount" column Si 1.43 30% C 1.95 40% O 1.43 30%
[0277] By calculation, SiOC derived from this formulation would contain a calculated 0.53 mol C after all CO removal and have a 63% C deficit or 63% C deficiency.
[0278] Example 9
[0279] The polysilicon carbide formulation was prepared by a mixing method. The formulation was prepared by mixing 70% MHF, 20% TV and 10% VT at room temperature. The precursor formulation contained 1.17 moles of hydride, 0.23 moles of vinyl, 0.0 moles of phenyl and 1.53 moles of methyl. The precursor formulation contained the following molar amounts and molar ratios of Si, C and O per 100 g.
[0280] element Molar amount Molar ratio of the total in the "Molar Amount" column Si 1.53 31% C 1.87 38% O 1.53 31%
[0281] By calculation, SiOC derived from this formulation would contain a calculated 0.33 mol C after all CO removal and have a 78% C deficit or 78% C deficiency.
[0282] Example 10
[0283] The polysilicon carbide formulation was prepared by a mixing method. The formulation was prepared by mixing 95% MHF and 5% TV at room temperature.
[0284] Example 11
[0285] Fig.11 The schematic cross-sectional view of an apparatus for growing SiC crystals and crystal structures is shown. The vapor deposition apparatus 1700 has a container 1701 connected (e.g., thermally connected, transmitting electromagnetic energy, surrounding) to a plurality of different heating elements (e.g., 1702). The heating elements are configured and operated to provide at least two different temperature zones: zone A 1702a and zone B 1702b. The container 1701 contains a polymer-derived ceramic 1703, which is a source of Si and C. In addition, the container 1701 contains a starting product 1704 from which the crystal is grown.
[0286] Thus, in summary, the polymer derived ceramic 1703 is heated in zone A 1702a to a temperature to sublime SiC, typically above about 2,000° C. The SiC vapor then rises into zone B 1702b, which is at a lower temperature than zone A 1702a. The SiC vapor is deposited as SiC on the starting article 1704.
[0287] It should be understood that the device 1700 is a great simplification for the purpose of illustrating the teachings, so that commercial and industrial devices may have additional components, such as control systems, monitors, gas processing equipment, etc., and may have different configurations. These additional components and different configurations, as well as possible modifications based on the teachings of the present invention, are readily understood by those skilled in the art.
[0288] Example 11a
[0289] In the vapor deposition apparatus 1701 , the polymer-derived ceramic 1703 is high-purity SiOC. The temperature of zone A is gradually increased and maintained at a certain temperature to convert the SiOC into SiC, and to sublime the SiC and form SiC crystals on the starting product 1704 .
[0290] Example 11b
[0291] In this example, the starting article 1704 is a seed crystal, and the SiC deposited from the polymer-derived SiC in region A forms an alpha single crystal pear-shaped crystal. The pear-shaped crystal is then sliced to form a polysilicon oxycarbide-derived SiC wafer.
[0292] Example 11c
[0293] In this example, the starting article 1704 is a Si substrate, and the polymer-derived SiC in region A is deposited on the substrate to form a polysilicon oxycarbide epitaxial layer on the Si substrate.
[0294] Example 11d
[0295] In the vapor deposition apparatus 1701 , the polymer-derived ceramic 1703 is high-purity SiOC with a purity of 6 9. The temperature of zone A is gradually increased and maintained at a certain temperature to convert the SiOC into SiC, and to sublime the SiC and form SiC crystals on the starting product 1704 .
[0296] Example 11e
[0297] In the vapor deposition apparatus 1701 , the polymer-derived ceramic 1703 is high-purity SiOC and contains less than 20 ppm of Al. The temperature of zone A is gradually increased and maintained at a certain temperature to convert the SiOC into SiC and to sublime the SiC and form SiC crystals on the starting product 1704 .
[0298] Example 11f
[0299] In the vapor deposition apparatus 1701, the polymer derived ceramic 1703 is high purity polysilicon oxycarbide derived SiC and contains less than 20 ppm Al. The SiC sublimates to form SiC crystals on the starting article 1704, which are the seeds.
[0300] Example 12
[0301] The vapor deposition apparatus 1701 is a hot wall reactor.
[0302] Example 13
[0303] The vapor deposition apparatus 1701 is a multiwafer reactor.
[0304] Example 14
[0305] The vapor deposition apparatus 1701 is a chimney reactor.
[0306] Example 15
[0307] A pear-shaped crystal of polysilicon oxycarbide derived SiC having a length of about 1 inch and a diameter of about 4 inches. The pear-shaped crystal is alpha-type and substantially free of micropipes. The pear-shaped crystal contains less than 100, less than 10, and preferably no micropipes.
[0308] Example 15a
[0309] A type with less than 10 / cm 2 , less than 5 / cm 2 , less than <1 / cm 2 , less than 0.5 / cm 2 , and most preferably less than 0.1 / cm 2 Figure 2. Microtube density of polysilicon oxide carbide derived SiC pear-shaped crystals.
[0310] Example 16
[0311] A metal-semiconductor field effect transistor (MESFET) made from polysilicon oxycarbide-derived SiC is incorporated into a compound semiconductor device and operates in the 45 GHz frequency range.
[0312] Example 17
[0313] A metal semiconductor field effect transistor (MESFET) made from polysilicon oxycarbide-derived SiC is incorporated into components of a cellular base station.
[0314] Example 18
[0315] A pear-shaped crystal of polysilicon oxycarbide derived SiC about 2 inches in length and about 4 inches in diameter.
[0316] The pear-shaped crystal is doped to form a p-wafer for a semiconductor device.
[0317] Example 19
[0318] A pear-shaped crystal of polysilicon oxycarbide derived SiC having a length of about 2 inches and a diameter of about 4 inches. The pear-shaped crystal is doped to form an n-wafer for semiconductor devices.
[0319] Example 20
[0320] Fig.12 Shown is a schematic cross-sectional view of an apparatus for growing SiC crystals and crystal structures. A vapor deposition apparatus 1800 has a container 1801 connected to a heat source 1802. The heat source, as well as the container and the heat source, can be any assembly described in the specification of the present invention or known in the art. The heat source is configured and operated to provide at least two different temperature zones: zone A 1802a and zone B 1802b. The container 1801 contains a polymer-derived ceramic 1803, which is a source of Si and C. The polymer-derived ceramic 1803 is the polysilicon oxide carbide in Example 6 that is cured and converted into SiC according to Example 14. In addition, the container 1801 contains a starting product 1804 from which the crystal is grown.
[0321] Thus, in summary, the polymer derived ceramic 1803 is heated in zone A 1802a to a temperature to sublime SiC, typically above about 2,400° C. The SiC vapor then rises into zone B 1802b, which is at a lower temperature than zone A. The SiC vapor is deposited as SiC on the starting article 1804.
[0322] It should be understood that the device 1800 is a great simplification for the purpose of illustrating the teachings, so that commercial and industrial devices may have additional components, such as control systems, monitors, gas processing equipment, etc., and may have different configurations. These additional components and different configurations, as well as possible modifications based on the teachings of the present invention, are readily understood by those skilled in the art.
[0323] Example 21
[0324] Fig.13Shown is a schematic cross-sectional view of an apparatus for growing SiC crystals and crystal structures. A vapor deposition apparatus 1900 has a container 1901 connected to a heat source 1902. The heat source, as well as the container and the heat source, can be any assembly described in the specification of the present invention or known in the art. The heat source is configured and operated to provide at least two different temperature zones: zone A 1902a and zone B 1902b. The container 1901 contains a polymer-derived ceramic 1903, which is a source of Si and C. The polymer-derived ceramic 1903 is the polysilicon carbide in Example 7 that is cured and converted into SiC according to Example 15. In addition, the container 1901 contains a starting product 1904 from which the crystal is grown.
[0325] Thus, in summary, the polymer derived ceramic 1903 is heated in zone A 1902a to a temperature to sublime SiC, typically above about 2,500° C. The SiC vapor then rises into zone B 1902b, which is at a lower temperature than zone A. The SiC vapor is deposited as SiC on the starting article 1904.
[0326] It should be understood that the device 1900 is a great simplification for the purpose of illustrating the teachings, so that commercial and industrial devices may have additional components, such as control systems, monitors, gas processing equipment, etc., and may have different configurations. These additional components and different configurations, as well as possible modifications based on the teachings of the present invention, are readily understood by those of ordinary skill in the art.
[0327] Example 22
[0328] Ultra-high purity SiOC provided by the formulation in the present specification and having a purity of at least about 5 9s, and preferably at least about 6 9s, is used to prepare transparent SiOC products in the process disclosed and taught in U.S. Patent No. 5,180,694. All disclosures of the above patents are incorporated into this application by reference.
[0329] Example 23
[0330] Ultra-high purity SiOC provided by the formulation of the present invention and having a purity of at least about 5 9s, and preferably at least about 6 9s, is used to prepare SiOC layers and article surface coatings, and is used in the process disclosed and taught in U.S. Patent No. 8,981,564.
[0331] Example 24
[0332] Ultra-high purity SiOC provided by the formulation of the present invention and having a purity of at least about 5 9s, and preferably at least about 6 9s, is used to prepare SiOC layers and article surface coatings, and is used in the process disclosed and taught in U.S. Patent No. 8,778,814.
[0333] Example 25
[0334] Polysilicon dioxide-derived SiC having a purity of 6 nines, and preferably 7 nines, or SiOC disclosed and taught for use in patent applications serial numbers 14 / 864,539 (U.S. Publication No. 2016 / 0208412), 14 / 864,125 (U.S. Publication No. 2016 / 0207782), and PCT / US2015 / 051997 (Publication No. WO 2016 / 049344) is used in this example, for example as a seed, starting crystal, source material, growth material, deposition material or raw material in the apparatus and process disclosed in U.S. patent application publication No. 2013 / 0255568, all disclosures of which are incorporated into this application by reference.
[0335] A method for preparing a silicon carbide single crystal having a diameter greater than 100 mm by sublimation comprises the following steps: preparing a seed substrate made of silicon carbide and a silicon carbide raw material; and growing the silicon carbide single crystal on the growth surface of the seed substrate by sublimating the silicon carbide raw material. In the step of growing the silicon carbide single crystal, the maximum growth rate of the silicon carbide single crystal on the growth surface of the seed substrate is greater than its maximum growth rate on the surface of the silicon carbide raw material. Therefore, when a silicon carbide single crystal having a diameter greater than 100 mm is grown, this embodiment can provide a method for preparing a silicon carbide single crystal that can obtain a thick film of a silicon carbide single crystal.
[0336] A method for preparing a silicon carbide single crystal in this embodiment is aimed at preparing a silicon carbide single crystal having a diameter greater than 100 mm by sublimation, and the method includes the following steps: preparing a seed crystal substrate made of silicon carbide and a silicon carbide raw material; and growing the silicon carbide single crystal on the growth surface of the seed crystal substrate by sublimating the silicon carbide raw material. In the step of growing the silicon carbide single crystal, the maximum growth rate of the silicon carbide single crystal on the growth surface of the seed crystal substrate is greater than its maximum growth rate on the surface of the silicon carbide raw material.
[0337] The above-mentioned preparation steps using the seed crystal substrate and the silicon carbide raw material are based on Figure 1Specifically, the silicon carbide raw material 7 is placed in the crucible 20. The seed crystal substrate 3 is placed in a position facing the silicon carbide raw material 7. The seed crystal substrate 3 is fixed by the seed crystal base 4. The seed crystal substrate 3 is made of a silicon carbide single crystal. The growth surface 6 of the seed crystal substrate 3 is a plane. The growth surface 6 can be a plane with an inclination angle of about 8°. Since the present embodiment corresponds to a method for preparing a silicon carbide single crystal having a diameter greater than 100 mm, the diameter of the seed crystal substrate 3 is also greater than 100 mm.
[0338] Preferably, in the step of growing the silicon carbide single crystal, the maximum height of the silicon carbide single crystal grown on the seed crystal substrate exceeds 20 mm, and more preferably, exceeds 50 mm. Figure 1 A further embodiment of the silicon carbide single crystal preparation apparatus embodiment shown will be based on Figure 2 To express.
[0339] The silicon carbide single crystal preparation device 10 according to the present embodiment is aimed at growing a silicon carbide single crystal having a diameter greater than 100 mm by sublimation. The preparation device 10 mainly includes a crucible 20 , a heater 2 and a hollow component 5 .
[0340] Crucible 20 is made of carbon. Silicon carbide raw material 7 is placed in crucible 20. Seed crystal substrate 3 is placed facing surface 8 of silicon carbide raw material 7. Seed crystal substrate 3 is fixed by seed crystal base 4. Base 4 is fixed by lid 12 of crucible 20.
[0341] A heater 2 is provided around the side wall 13 of the crucible 20 to heat the silicon carbide raw material 7 placed in the crucible 20. Preferably, the heater 2 is provided to cover the entire bottom 11 of the crucible 20. The heater 2 may be an induction heating type heater or a resistance heating type heater.
[0342] The hollow part 5 is hollow. The hollow part 5 is provided to extend from the middle upper end surface of the bottom 11 of the crucible 20 toward the seed crystal substrate 3. The hollow part 5 is surrounded by the silicon carbide raw material 7. Preferably, the hollow part 5 is embedded in the silicon carbide raw material 7. The height of the hollow part 5 is lower than that of the silicon carbide raw material 7. In addition, the heater 2 is placed below the hollow part 5. Since the hollow part 5 is hollow, the surface of the silicon carbide raw material 7 around the central area can be effectively heated by radiation. Therefore, this reduces the temperature distribution of the silicon carbide raw material. Optionally, the crucible 20 may have a bottom shaped to protrude toward the seed crystal substrate 3 in the central area, rather than the hollow part 5.
[0343] The thickness of the bottom 11 of the crucible 20 is preferably greater than 10 mm. More preferably, the thickness is greater than or equal to 20 mm. Accordingly, the bottom 11 of the crucible 20 can be heated by heat conduction of carbon having a higher thermal conductivity than silicon carbide. Then, the silicon carbide single crystal growth step is performed. Specifically, the silicon carbide raw material 7 placed in the crucible 20 is heated to sublime the silicon carbide raw material. The sublimated raw material gas is recrystallized on the growth surface 6 of the seed crystal substrate 3, whereby the silicon carbide single crystal grows on the growth surface 6.
[0344] If a larger size of silicon carbide single crystal is to be grown, the inner diameter of the crucible 20 used must also be increased. If the inner diameter of the crucible 20 is increased, the distance from the heater 2 placed outside the crucible 20 to the center "b" of the surface 8 of the silicon carbide raw material 7 (i.e., the area of the surface 8 of the silicon carbide raw material 7 facing the center "a" of the seed crystal substrate 3) becomes longer. Therefore, since the area around the center "b" of the surface 8 of the silicon carbide raw material 7 cannot be heated instantly, the temperature distribution of the silicon carbide raw material 7 will increase.
[0345] If the temperature around the center "b" of the surface 8 of the silicon carbide raw material 7 becomes relatively low, the sublimated silicon carbide gas will recrystallize on the surface 8 of the silicon carbide raw material 7. Therefore, silicon carbide crystals will also grow on the surface 8 of the silicon carbide raw material 7. If silicon carbide crystals grow on the surface 8 of the silicon carbide raw material 7, the space available for the growth of silicon carbide single crystals on the growth surface 6 of the seed crystal substrate 3 will become smaller, which makes it difficult to grow a thick film of silicon carbide single crystals.
[0346] According to the method for preparing a silicon carbide single crystal of the present embodiment, the maximum growth rate of the silicon carbide single crystal on the growth surface 6 of the seed substrate 3 is greater than its maximum growth rate on the surface 8 of the silicon carbide raw material 7. Therefore, if a silicon carbide single crystal having a diameter greater than 100 mm is grown, a thick film of a silicon carbide single crystal can be obtained. In addition, the growth rate of the silicon carbide crystal on the surface 8 of the silicon carbide raw material 7 can be increased. In addition, since the growth of the silicon carbide crystal on the surface 8 of the silicon carbide raw material 7 can be suppressed, the change in the growth environment of the silicon carbide single crystal on the seed substrate 3 can be reduced. Accordingly, the occurrence of crystal defects in the silicon carbide single crystal can be reduced.
[0347] According to the method for preparing a silicon carbide single crystal of the present embodiment, in the step of growing a silicon carbide single crystal, the sublimation of the silicon carbide raw material is performed by radiant heating of the area on the surface 8 of the silicon carbide raw material 7 facing the center of the seed crystal substrate 3. Accordingly, the temperature distribution of the silicon carbide raw material 7 can be reduced. Therefore, a thick film of a silicon carbide single crystal can be grown on the seed crystal substrate 3 by suppressing the growth of the silicon carbide crystal on the silicon carbide raw material 7.
[0348] The method for preparing a silicon carbide single crystal of the present embodiment is implemented by heating the silicon carbide raw material through the hollow member 5. Accordingly, the surface 8 of the silicon carbide raw material 7 around the central region can be heated more efficiently by radiation, which can reduce the temperature distribution of the silicon carbide raw material 7. Therefore, a thick film of a silicon carbide single crystal can be grown on the seed crystal substrate 3 by suppressing the growth of the silicon carbide crystal on the silicon carbide raw material 7.
[0349] Example 26
[0350] 6-9 pure, and preferably 7-9 pure (higher purity is also possible) polysilicon carbide derived SiC or SiOC disclosed and taught for use in patent applications serial numbers 14 / 864,539 (U.S. Publication No. 2016 / 0208412), 14 / 864,125 (U.S. Publication No. 2016 / 0207782) and PCT / US2015 / 051997 (Publication No. WO 2016 / 049344) is used in this embodiment, for example as a seed crystal, starting crystal, source material, growth material, deposition material or raw material in the apparatus and process disclosed in U.S. Patent No. 8,216,369, all disclosures of which are incorporated into this application by reference.
[0351] Silicon carbide (SiC) has unique electrical properties that make it a suitable material for the manufacture of the latest semiconductor devices that operate at high frequencies, high voltages, high current densities and in harsh conditions. In many of these devices, silicon carbide is used as a substrate for the semiconductor device structure to be formed by epitaxy, photolithography and metallization. Depending on the design of the device, the substrate must have specific electrical parameters such as conductivity type and resistivity. Devices operating at high frequencies and microwave frequencies (RF devices) require the use of semi-insulating (SI) substrates with very high resistivity, while other devices such as high-power conversion devices require the use of low-resistivity n-type and p-type substrates.
[0352] Currently, SiC single crystals are grown on an industrial scale by a sublimation technique called physical vapor transport (PVT). Figure 3Schematic diagram of the arrangement of a PVT device in the prior art. In PVT, polycrystalline particles of silicon carbide (SiC source) are loaded on the bottom of a growth container 32, and SiC seeds are attached to the top of the growth container 32 by 34. Preferably, the growth container 32 is made of a material that does not react with SiC or any dopants added (discussed below), such as graphite. The loaded growth container 32 is evacuated, filled with an inert gas to the required specific pressure and heated to a growth temperature, such as between 1,900°C and 2,400°C, by at least one heating element 33 (such as a radio frequency coil). The growth container 32 is heated to produce a longitudinal temperature gradient, which makes the temperature of the SiC source 31 higher than the temperature of the SiC seed crystal 34. At high temperature, the silicon carbide of the SiC source 31 sublimates, releasing a series of volatile molecular species into the vapor phase. The most abundant of these gas molecular species are Si, Si 2 C and SiC 2 Driven by the temperature gradient, these gas molecules are transported to the SiC seed crystal 34 and condensed on its surface, so that the SiC single crystal 35 grows on the SiC seed crystal 34. Prior art related patents in this field include U.S. Patent Nos. 6,805,745, 5,683,507, 5,611,955, 5,667,587 and 5,746,827; and Re. 34,861, all of which are incorporated into this application by reference.
[0353] It will be appreciated by those skilled in the art of semiconductor materials that it is not possible to prepare a SiC substrate with desired electrical properties without adding specific impurities to the SiC substrate through a process known as doping. In silicon carbide, chemical bonds are so strong and solid phase diffusion of impurities is so slow that the bulk doping process can only be accomplished during the crystal growth stage, when the doping elements (dopants) are added directly to the lattice of the growing SiC crystal 35.
[0354] As a specific example of doping during SiC growth, n-type SiC crystals are grown by adding a small amount of gaseous nitrogen (N 2 Nitrogen-doped SiC single crystals with highly uniform electrical properties can be prepared by maintaining appropriate N during the growth process. 2 Partial pressure and direct growth.
[0355] Achieving uniform electrical properties in other SiC crystals, including semi-insulating, p-type, and phosphorus-doped n-type crystals, is much more difficult except for nitrogen-doped crystals because the doping compounds are solid rather than gaseous. Vanadium is a particularly important dopant used to make high-resistivity semi-insulating SiC crystals. Aluminum is another important dopant used in the growth of p-type conducting crystals. Other solid-state dopants include boron, phosphorus, heavy metals, and rare earth elements.
[0356] The existing SiC crystal doping technology using solid dopants is implemented by directly doping a small amount of impurities into the SiC source 31. For example, vanadium can be introduced in the form of elemental vanadium, vanadium carbide or vanadium silicide; aluminum can be introduced in the form of elemental aluminum, aluminum carbide or aluminum silicide; other suitable solid dopants, such as boron or phosphorus, can also be introduced in the form of elemental, carbide or silicide. The physical form of the doping compound can be powder, small pieces or flakes.
[0357] During the growth of the SiC crystal 35 sublimate, there are multiple chemical reactions between the SiC source 31 and the dopant directly doped. These reactions proceed in several stages and produce intermediary compounds. For vanadium doping, thermodynamic analysis shows that the product of the reaction between SiC and vanadium dopant (element, carbide or silicide) depends on the stoichiometry of SiC, that is, when the SiC source 31 is Si-rich and its composition reaches a two-phase equilibrium between SiC and Si, it is very likely to produce vanadium silicide (VSi 2 ); When the SiC source 31 is C-rich and its composition reaches a two-phase equilibrium between SiC and C, it is very likely to produce vanadium carbide (VC x ).
[0358] As is known, the newly synthesized SiC source 31 is typically silicon-rich. Due to the inconsistency of SiC sublimates, the silicon-rich SiC source 31 gradually becomes carbon-rich. The stoichiometric change of the SiC source 31 during the sublimation growth process may cause the following sequence of reactions:
[0359] In the initial stage of growth, the SiC source 31 is rich in silicon, and the reaction between the vanadium dopant and SiC produces vanadium silicide VSi 2 As the growth progresses and the SiC source 31 is enriched with carbon, the vanadium silicide is transformed into the carbon silicide intermediate VC x Si y ; In the final stage of growth, the SiC source 31 is rich in carbon, and the vanadium carbide is converted into vanadium carbide VC xThe physical vapor transport system includes a growth chamber containing a source material and a seed crystal placed at a distance, and at least one capsule having at least one capillary extending between the inside and the outside thereof, wherein the inside of the capsule is filled with a dopant. Each capsule is installed in the growth chamber. Through a growth reaction performed in the growth chamber in which the capsule is installed, a crystal can be formed on the seed crystal using the source material, wherein the formed crystal is doped with the dopant.
[0360] according to Figure 4 The advantages of spatial uniformity and controlled doping are achieved by using a delayed release capsule 44 which contains the solid dopant in a stable form and is placed within the growth vessel 32 (see Figure 3 ). The capsule 44 is preferably made of an inert material that does not react with either SiC or the dopant. For most applications, dense and low-porosity graphite is the preferred material for the capsule 44. Other possible materials include refractory metals, their carbides and nitrides. However, this should not be construed as a limitation to this embodiment.
[0361] The capsule 44 includes a tight fitting lid 45 including one or more calibrated through holes or capillaries 46 of predetermined diameter and length. The size of the capsule 44 is not limited except that it can fit into the growth vessel 32 and does not restrict the flow rate of vapor moving toward the SiC seed crystal 34.
[0362] When appropriate, the capsule 44 is loaded with an appropriate amount of solid dopant 47. The dopant 47 must be in a stable chemical form that does not react with the constituent materials of the capsule 44, or in a chemical form that can react with the constituent materials of the capsule 44 to produce a stable compound. For most practical applications, the preferred forms of the solid dopant are: (1) a single substance; (2) a carbide and (3) a silicide. However, this should not be construed as limiting this embodiment.
[0363] During the sublimation growth of SiC crystal 35 , capsule 44 is placed in growth container 32 .
[0364] In one embodiment, Figure 5a As shown, a single capsule 54 is placed on the upper surface of the SiC source and close to the axis of the growth container 52. In another embodiment, as shown in FIG. Figure 5b As shown, several capsules 54 are placed on the upper surface of the SiC source and close to the side wall of the growth container 52. In another embodiment, as shown in FIG. Figure 5c As shown, capsule 54 is embedded in the material forming the SiC source.
[0365] The working principle of capsule 54 is based on the known phenomenon of effusion, i.e., the slow escape of vapor from a sealed container through small holes. At high temperatures, the vapor pressure of the dopant in the capsule forces the vapor to escape through the capillaries. If the cross-section of the capillaries is small enough, there is no substantial difference between the vapor pressure of the dopant in the capsule and the equilibrium value.
[0366] The gap flow law is well known, and the outflow of dopant molecules from capsule 54 through each capillary can be easily calculated when the growth conditions (temperature, vapor pressure of the inert gas, volatility of the substances contained in capsule 54) are known. Therefore, the size of each capillary and the number of capillaries can be tailored to obtain a stable, well-controlled outflow of dopant vapor from capsule 54 for SiC crystal growth.
[0367] For relatively low doping levels, a capsule 54 with a single capillary can be used (see the embodiment shown in FIG. 5 a). For relatively high doping levels or doping with multiple dopants, multiple capsules 54 can be used (see Figure 5b For special purposes, such as programmable or delayed doping, one or more delayed release capsules 54 can be used, which are buried deep in the SiC source (see Figure 5c embodiment shown).
[0368] According to the prior art of SiC doping, a small amount of dopant is directly doped into the SiC source material, which causes a chemical reaction between the dopant and the SiC source. These reactions, together with the change in the stoichiometry of the SiC source material, can lead to a gradual change in the partial pressure of the dopant. Therefore, the prior art doping technology can produce an initial high concentration of dopants in the crystal, and as the length of the SiC crystal increases, the concentration of the dopant decreases. The crystal grown according to the prior art has an excessively high doping level in the first grown part, while the doping level in the later grown part is insufficient. Among them, the doping level of the first grown part is so high that a second phase precipitate is formed in the crystal block, which leads to the generation of crystal defects.
[0369] This embodiment eliminates the problems existing in the prior art by using one or more delayed release capsules to dope SiC crystals during the crystal growth process. This embodiment has two obvious advantages:
[0370] First, the present embodiment avoids direct contact between the dopant and the SiC source. This is achieved by placing the dopant inside a capsule made of an inert material.
[0371] Secondly, this embodiment provides a method for accurately controlling the concentration of dopants by selecting the number of capsules, the number and size of capillaries, and the position of each capsule in the growth container.
[0372] This embodiment provides the following technical advantages over the prior art: first, this embodiment avoids direct contact between the dopant and the SiC source, thereby avoiding or eliminating the intermediate process associated with the chemical reaction between the dopant and the SiC source; second, this embodiment provides a method for accurately controlling the flow of the dopant toward the SiC seed crystal. The above technical advantages can help prepare SiC crystals with precise and uniform doping.
[0373] The direct benefit of precise and spatially uniform doping is that SiC crystals with spatially uniform and controllable electrical properties can be prepared. In addition to excellent electrical properties, this embodiment avoids or eliminates the generation of impurity precipitation and related defects, thereby improving the quality of the prepared SiC crystals.
[0374] In particular, for vanadium-doped SiC crystals, the application of this embodiment will increase the yield of usable high-quality SiC wafers by 50%, which will ultimately reduce costs and increase profits.
[0375] This embodiment can be applied to the growth of vanadium-doped semi-insulating 6H-SiC single crystals. However, this should not be understood as a limitation of this embodiment, because it is expected that this embodiment can also be applied to the growth of 4H-SiC, 3C-SiC or 15R-SiC single crystals doped with suitable dopants. In Examples 2 and 3, a delayed release capsule made of pure dense graphite was used. All other parameters of the SiC growth process, such as temperature, pressure, temperature gradient, etc., are consistent with the parameters in the existing growth technology for preparing SiC crystals.
[0376] Example 27
[0377] 6 9 pure, and preferably 7 9 pure (higher purity is also possible) polysilicon oxycarbide derived SiC or SiOC disclosed and taught for use in patent applications Nos. 14 / 864,539 (U.S. Publication No. 2016 / 0208412), 14 / 864,125 (U.S. Publication No. 2016 / 0207782), and PCT / US2015 / 051997 (Publication No. WO 2016 / 049344) are used in this embodiment, for example as a seed, starting crystal, source material, growth material, deposition material, or raw material in the apparatus and process disclosed in U.S. Patent No. 8,512,471, all disclosures of which are incorporated herein by reference. Ultra-high purity SiC material greatly improves the process and apparatus in the 8,512,471 patent by improving or directly eliminating the methods and apparatus used in the patent for removing boron and other impurities.
[0378] In the physical vapor phase growth technology of silicon carbide, this embodiment introduces a silicon carbide powder and a silicon carbide seed into a physical vapor phase growth system, and introduces halogenated silane (halosaline) gas separately into the system. The silicon carbide powder, halogenated silane and seed are heated to promote the physical vapor phase growth of silicon carbide on the crystal, and the chemical conversion between the halogen and the chemical elements in the growth system.
[0379] Physical vapor transport (PVT) is the most common sublimation technique used for SiC crystal growth. Figure 6 Schematic diagram of a common PVT arrangement. Typically, crystal growth is carried out in a graphite crucible 61, which is sealed by a graphite cover 62 and carries a sublimation source 63 and a seed crystal 64. Typically, a polycrystalline SiC source 63 is placed at the bottom of the crucible 61, and a SiC seed crystal is placed at the top of the crucible 61. The seed crystal 64 is usually mounted directly to the crucible cover 62 by using an adhesive or other means. The crucible 61 is heated to the growth temperature, typically between 2,000°C and 2,400°C, at which time the source 63 evaporates and sublimates as a volatile molecular species Si 2 C. SiC 2 The crucible 61 is filled with Si in the form of a source 63. During the growth process, the temperature of the source 63 is kept higher than the temperature of the seed crystal 46. The temperature difference forces the vapor to migrate from the source 63 to the seed crystal 64 and deposit on the seed crystal 64 to form a single crystal 65. In order to control the growth rate and ensure high crystal quality, PVT growth is carried out in a low-pressure inert gas, which is usually in the range of several Torr to 200 Torr.
[0380] As is known, the permeability of graphite depends on the nature of the gas diffusing through it. Graphite is generally permeable to inert gases, hydrogen and nitrogen, but much less permeable to elements that form stable carbides. Correspondingly, graphite is also very permeable to the vapors formed during the sublimation of silicon carbide, such as Si, Si 2 C and SiC 2 Thus, conventional PVT can be considered a "closed" process, in which Si-bearing vapor rarely leaves the crucible, except for a small amount of unintentional escape through the connection between the crucible 61 and the crucible cover 62.
[0381] SiC single crystals can also be grown using an "open" process in which a gas flow is intentionally established between the inside and outside of the crucible, such as high temperature chemical vapor deposition (HTCVD), halide chemical vapor deposition (HCVD), and certain PVT modifications. Figure 7 Schematic diagram of a generalized open SiC growth process. Similar to the closed sublimation growth process, the open growth process is also carried out in a graphite crucible 71, wherein the source 73 is placed at the bottom of the crucible and the seed 74 is placed at the top of the crucible. The graphite crucible 71 used in the open process is provided with an inlet 77 and an outlet 79. A gas mixture 76, which may contain Si precursors, C precursors, dopants and other gas components, enters the crucible through the inlet 77. After entering the crucible 71, the reactants undergo chemical transformation in the reaction zone 78. The gaseous reaction products mix with the vapor from the solid source 73 and move toward the seed 74, and then deposit on the seed 74 to form a single crystal 75. The gaseous byproducts overflow through the outlet 79. In the HCVD process, silicon and carbon precursors are reacted in the form of silicon tetrachloride (SiCl 4 ) and propane (C 3 H 8 ) is transported to the reaction zone 78 in the form of a molten-silicon-based SiC substrate. The main disadvantage of this open SiC sublimation growth process is the severe loss of Si-carrying vapor, which overflows through the gas outlet 79.
[0382] Graphite is widely used in SiC sublimation growth as a component material for crucibles, seed holders, heat shields and other components. The starting materials used in graphite manufacturing (coke and pitch) contain boron, so boron is always present in graphite, with its atoms chemically bound to carbon atoms. High temperature treatment in a halogen-containing atmosphere is widely used by graphite manufacturers for purification. During the purification process, the halogen molecules penetrate the graphite block, react with a variety of different impurities and form volatile halides. Driven by the concentration gradient, the halide molecules diffuse from the graphite block toward the surface, where they are blown away by the carrier gas flow. Generally, the removal of metal impurities in graphite is more efficient than the removal of boron.
[0383] By convention, graphite manufacturers define the purity of graphite in terms of "ash content," which is the amount of ash that remains after a sample of graphite is burned in oxygen. The highest purity graphite available commercially contains 5 to 20 ppm ash by weight. Boron forms volatile oxides by combustion in oxygen; therefore, graphite manufacturers rarely specify the boron content of their graphite. Impurity analysis using glow discharge mass spectroscopy (GDMS) shows that even the ash-free graphites typically contain more than 0.2 ppm boron, and in some cases up to 1 ppm.
[0384] The furnaces used for graphite purification are usually very large and can hold several metric tons of graphite. Cross contamination between different items within the same furnace of graphite and contamination from the furnace itself limits the purification efficiency. Therefore, graphite with a boron content of less than 0.1 ppm (by weight) is not readily available on a regular commercial basis.
[0385] Optimization of conventional PVT sublimation growth, including application of a protective coating to the inner surface of the graphite crucible, has reduced the boron content of the grown SiC crystals to (2-3)·10 16 cm -3 However, in order to produce semi-insulating SiC crystals with higher quality and excellent electrical parameters, the content of unintentional boron doping must be reduced to less than 10 16 cm -3 .
[0386] If the boron is removed from the growth crucible simultaneously during the crystal growth process, the unintentional doping boron content in the SiC crystal will be greatly reduced. It is believed that such in-situ purification during the growth of SiC crystals is unknown in the prior art to date.
[0387] SiC sublimation growth utilizes crucibles, seed crystal holders, and other components made of graphite. Typically, graphite contains detectable levels of boron impurities, which can contaminate the growing crystal. To address this problem, SiC sublimation growth is performed in a dynamic reactive atmosphere that includes an inert carrier gas and at least one reactive gas. The reactive gas stream is fed into the graphite growth crucible through a gas inlet and filtered out of the crucible through the permeable crucible wall.
[0388] The main reactive component of the gas mixture is a silane halide gas, preferably a tetrahalosilane, such as tetrachlorosilane (SiCl 4 ) or silane tetrafluoride (SiF 4 ). The silane halide additive is added to the gas mixture at a concentration between 0.1% and 10% (by volume), more preferably between 1% and 5%. At the high temperature of SiC sublimation growth, the silane halide undergoes pyrolysis and forms lower silane halide, such as SiCl 3 With SiCl 2 The pyrolysis products react with boron to produce volatile boron halides, such as BCl, BCl 2 With BCl 3 The boron-containing by-products are removed from the crucible by the gas mixture flowing through the permeable crucible wall.
[0389] Lower (halogenation degree) halogenated silanes can attack the SiC source and grow crystals, causing a loss of silicon in the growth. In order to reduce this loss, the gas mixture may contain a small amount of hydrogen, preferably between 0.1% and 3% (by volume). The presence of hydrogen changes the thermodynamic equilibrium in the gas phase, thereby reducing the chemical attack of the halogenated silane on the SiC source and the crystal.
[0390] The grown crystals are characterized by the concentration of unintentionally doped boron acceptors below 7·10 15 cm -3 , and the resistivity is higher than 10 7 Ohm·cm.
[0391] The present embodiment discloses a crystal growth method, the method comprising: (a) providing a closed growth crucible in a growth chamber, wherein a heat insulating layer is provided between the growth chamber and the growth crucible, the growth crucible having a polycrystalline source material and seed crystals placed at intervals; (b) heating the interior of the growth crucible to form a temperature gradient between the source material and the seed crystals, heating the source material to a sublimation temperature, and making the temperature gradient sufficient to transport the sublimated source material to the seed crystals for deposition; and (c) flowing a gas mixture into the growth crucible and between the polycrystalline source material and the inner surface of the growth crucible, the gas mixture reacting with unwanted elements in the growth crucible to form gaseous byproducts, the byproducts flowing through the crucible to the surface of the crucible under the driving force of the gas mixture flowing into the growth crucible, wherein the surface of the crucible is formed of a material that is permeable to the gas mixture and the gaseous byproducts, the unwanted element is boron, and the gas mixture comprises (i) A combination of a halosilane and (ii) an inert gas.
[0392] The inert gas may be argon or helium.
[0393] The halogenated silane gas may be tetrahalogenated silane, and its volume concentration in the gas mixture is between 0.1% and 10%, or between 1% and 5%.
[0394] The gas mixture may further comprise hydrogen gas, the volume concentration of which in the gas mixture may be between 0.1% and 3%.
[0395] The polycrystalline source material may be placed in a source crucible, wherein the source crucible is placed within the growth crucible and spaced from the inner surface of the growth crucible. The outer side of the bottom of the source crucible may be placed spaced from the outer side of the bottom of the growth crucible, thereby forming a first gap. The outer side of the wall of the source crucible may be placed spaced from the inner side of the wall of the growth crucible, thereby forming a second gap. The gas mixture may flow into the first and second gaps.
[0396] The flow rate of the gas mixture may be between 20 and 200 seem.
[0397] The thickness of the wall of the growth crucible may be between 4 mm and 20 mm, or between 8 mm and 16 mm.
[0398] The growth crucible may be made of graphite. The growth chamber may be made of fused silica. The thermal insulation layer may be made of porous graphite.
[0399] This embodiment also discloses a crystal growth method, which includes: (a) providing a seed crystal and a source material in a growth crucible, wherein the seed crystal and the source material are placed at intervals, and the growth crucible is prepared from a material that is at least partially gas-permeable, and the material contains elements that are not required to be present in the crystal grown in the growth crucible; (b) heating the growth chamber so that the source material sublimates and is transported to the seed crystal for deposition through the temperature gradient in the growth chamber; and (c) while (b) is being performed, allowing a gas mixture to flow into the growth crucible so that unnecessary elements in the growth crucible react with the gas mixture and are transported to the outside of the growth crucible through at least the gas-permeable portion of the growth crucible.
[0400] The gas mixture may be passed through the growth crucible at a flow rate between 20 and 200 seem.
[0401] The source material may be placed in a source crucible, wherein the source crucible is placed in the growth crucible. The outer wall of the source crucible may be spaced apart from the inner wall of the growth crucible, and the spacing distance may be between 4 mm and 7 mm.
[0402] The undesirable element may be boron. The gas mixture may be a combination of (i) a silane halide gas and (ii) an inert gas.
[0403] The growth crucible may include graphite.The source material and the seed crystal may include SiC.
[0404] according to Figure 8 More specifically, the PVT sublimation growth of silicon carbide is carried out in a graphite growth crucible 81 sealed by a graphite cover 62. Preferably, the crucible 81 and the cover 82 are made of high-density, fine-grained and low-porosity graphite, such as the one available under the registered trademark (Registration No. 1008278) provided by Union Carbide Corporation of Danbury, Conn. "ATJ", or the like. Growth crucible 81 carries SiC polycrystalline source 83 and amorphous seed 84. Source 83 is placed in the lower part of crucible 81, while seed 84 is placed on the top of crucible 81, preferably attached to crucible cover 82, such as Figure 8 As shown. The source 83 is contained in a thin-walled graphite source crucible 83a, which rests on a graphite pedestal 83b. For the dimensioning of the growth crucible 81, the source crucible 83a and the pedestal 83b, a gap 810 exists between the wall of the source crucible 83a and the wall of the growth crucible 81. Preferably, the width of the gap 810 is between 4 mm and 7 mm.
[0405] The growth crucible 81 with the source 83 and the seed 84 is placed in the chamber 820 of the growth station and is surrounded by an insulation layer 812. The insulation layer 812 is made of a lightweight fibrous graphite, such as graphite felt or graphite foam. The growth station can heat the growth crucible 81 to the growth temperature. In a specific embodiment, the chamber 820 is water-cooled and made of fused quartz, and the heating is achieved by an external radio frequency (RF) coil 823. Metal chambers with internal resistance heaters or RF coils can also be used.
[0406] To start sublimation growth, crucible 81 is heated to a growth temperature, preferably between 2,000° C. and 2,400° C. At the growth temperature, SiC source 83 sublimates and fills crucible 81 with vapor containing Si, Si 2 C and SiC 2 During the growth process, the temperature of the source 83 is kept higher than the temperature of the seed crystal 84, which causes the vapor to be transported from the source 83 to the seed crystal 84. After reaching the seed crystal 84, the vapor condenses on the surface of the seed crystal 84 and grows a SiC single crystal 85.
[0407] During the growth of SiC single crystal 85, a gas mixture 86 is supplied into growth crucible 81, wherein the gas mixture 86 first passes through gas inlet 821 of chamber 820 and then through gas inlet 87 of growth crucible 81. After entering growth crucible 81, the gas mixture 86 flows into gap 810 formed between the wall of growth crucible 81 and the wall of source crucible 83a through window 8W of base frame 83b, as shown in FIG. Figure 8 shown.
[0408] The gas mixture 86 supplied to the growth crucible 81 comprises an inert carrier gas, preferably argon or helium, and one or more reactive gas additives. The main reactive additive is a silane halide gas, preferably silane tetrahalide (SiCl 4 or SiF 4 ). The volume concentration of the silane halide in the gas mixture is preferably between 0.1 and 10%, and more preferably between 1 and 5%. The gas mixture may contain another reactive gas additive, such as hydrogen, the volume concentration of which is preferably between 0.1 and 3%.
[0409] The halogenated alkane gas reacts with boron and converts it into volatile boron halides within the growth crucible 81. These gaseous boron byproducts are removed from the interior of the growth crucible 81 by filtering through the permeable walls of the growth crucible 81. Thereafter, these byproducts are removed from the growth chamber 820 through the gas outlet 822 under the flow of the gas mixture 86.
[0410] The chemical form of boron under SiC sublimation growth conditions is uncertain. It is speculated that at high temperatures and in the presence of carbon and SiC, boron is in the form of elemental boron vapor, or a compound with carbon, or a compound with silicon. According to the general view, the boron contained in the graphite bulk is chemically combined with carbon to form a boron carbide (B 4 C) similar chemical bonds.
[0411] At the high temperature of SiC sublimation growth, the silane halide additive undergoes pyrolysis. The pyrolysis of tetrahalogenated silane produces lower (halogenated) silane halides, such as SiCl 4 The main product of pyrolysis is SiCl 2 With SiCl 3 Thermodynamic analysis shows that, regardless of the chemical form of boron, either in elemental form or in combination with carbon or silicon, the lower silane halides will react with boron-containing molecules to produce volatile boron halides such as BCl, BCl 2 With BCl 3 .
[0412] Argon and helium, as well as boron halide gas, are sufficiently permeable in graphite. Therefore, the boron byproduct gas can be effectively removed by establishing a flow of the boron byproduct gas through the permeable wall of the crucible 81. This can be achieved by flowing the carrier gas 86 through the permeable wall of the crucible 81. Figure 8 As shown, arrows 811 represent the removal of boron halide byproducts as the carrier gas flows through the crucible wall.
[0413] Another advantage of the silane halogenide reactive additive is that it reacts with the boron contained in the graphite mass. When filtering through the crucible wall, the carrier gas 86 carries the silane halogenide pyrolysis products into the graphite mass, where the pyrolysis products react with the boron chemically bonded to the carbon. The flow of the inert carrier gas 86 through the crucible wall promotes the removal of volatile boron halides out of the growth crucible 81.
[0414] At high temperatures, some products of the pyrolysis of the halogenated silane can attack the SiC source 83 and grow crystals 85. For example, a higher (halogenated) halogenated silane SiCl 3 Can attack SiC to produce free carbon and lower (halogenated) silane halides SiCl 2 This process can result in the removal of silicon from the growth crucible 81, the loss of silicon in the SiC source 83, and the erosion of the SiC crystal. To avoid this phenomenon, the gas mixture supplied to the crucible 81 contains a small amount of hydrogen. The presence of hydrogen in the gas phase will produce a small amount of hydrogen halide (SiCl 4 In the case of HCl, SiF 4In this case, HF) is used to change the thermodynamic equilibrium, thereby greatly reducing the attack on the SiC source 83 and the crystal 85. To achieve this purpose, the volume concentration of hydrogen in the gas mixture is preferably between 0.1 and 3%.
[0415] To effectively remove boron, the flow rate of the gas mixture is preferably between 20 sccm and 200 sccm. Too high a flow rate may create harmful overpressure inside crucible 81 and / or interfere with the crystal growth process, while too low a flow rate may be ineffective or cause Si-bearing vapor to escape from crucible 81 through gas inlet 87.
[0416] The crucible wall must be thin enough to allow the volatile boron halide to escape by leaching / diffusion. At the same time, the crucible wall must not be too thin, otherwise it will not be able to carry Si vapor (such as SiC 2 、Si 2 C) is completely transparent and will result in loss of Si from the crystal growth source 83. Preferably, the thickness of the graphite crucible wall is between 4 mm and 20 mm, more preferably between 8 mm and 16 mm.
[0417] In summary, the removal of boron from the growth crucible is carried out in situ during the growth of the SiC crystal. To this end, a gas reaction mixture is fed into the growth crucible through a gas inlet and overflows from the crucible by filtering through the permeable crucible wall. The gas mixture comprises an inert carrier gas and a silane halide gas, wherein the silane halide gas is preferably SiCl 4 or SiF 4 , the volume concentration of the silane halide gas in the gas mixture is preferably between 0.1 and 10%, more preferably between 1 and 5%. More preferably, a small amount of hydrogen is added to the gas mixture, with a volume concentration between 0.1 and 3%. At high temperature, the silane halide additive is pyrolyzed. The pyrolysis products react with boron, including boron contained in graphite. The reaction produces volatile boron halides. Subsequently, the boron halides are removed from the growth crucible by filtering through the permeable crucible wall, and this process is assisted by the flow of the carrier gas. The hydrogen addition reduces the chemical attack on the SiC source and crystal, and the loss of silicon in the growth crucible. The concentration of unintentionally doped boron acceptors in the grown crystal 85 is less than 7·10 15 cm -3 , and the resistivity is higher than 10 7 Ohm·cm.
[0418] In summary, the foregoing description discloses:
[0419] A process for sublimation growth of a SiC single crystal, wherein the growth is carried out in a dynamic reactive atmosphere.
[0420] Application of reactive atmosphere in SiC sublimation growth, wherein the reactive atmosphere comprises an inert carrier gas, preferably pure argon or helium mixed with reactive gas additives.
[0421] Application of a reactive gas additive, wherein the reactive gas additive comprises a halogenated silane, preferably SiCl 4 or SiF 4 .
[0422] Application of reactive atmosphere in SiC sublimation growth, wherein the reactive atmosphere comprises a combination of halogenated silane and hydrogen.
[0423] The use of a reactive atmosphere in SiC sublimation growth, wherein the volume concentration of the silane halide is preferably between 0.1 and 10%, and more preferably between 1 and 5%.
[0424] Application of reactive atmosphere in SiC sublimation growth, wherein the volume concentration of hydrogen is preferably between 0.1 and 3%.
[0425] A process for PVT sublimation growth under a continuous flow of a reactive gas mixture, wherein the reactive gas mixture enters the growth crucible through a gas inlet and escapes from the growth crucible by filtering through a permeable wall of the growth crucible.
[0426] A process of PVT sublimation growth under continuous gas flow, wherein the flow rate of the continuous gas flow is preferably between 10 sccm and 200 sccm, and more preferably between 20 sccm and 100 sccm.
[0427] A growth crucible made of dense, fine-grained graphite with low porosity, the wall thickness of which is preferably between 4 mm and 20 mm, and more preferably between 8 mm and 16 mm.
[0428] A SiC sublimation growth process, wherein a SiC source is contained in a thin-walled source crucible placed in a growth crucible, and a gap is formed between the bottom surface and side wall of the growth crucible and the bottom surface and side wall of the source crucible, respectively. The width of the gap is preferably between 2 mm and 10 mm, and more preferably between 4 mm and 7 mm.
[0429] With a concentration lower than 7.10 15 cm -3 SiC single crystals of 4H, 6H, 15R and 3C polytypes unintentionally doped with boron acceptors.
[0430] The technical advantages of the method and apparatus described above include:
[0431] The concentration of unintentionally doped boron acceptors in 6H and 4H SiC crystals was reduced.
[0432] Achieving higher and more spatially uniform resistivity in semi-insulating SiC crystals; and
[0433] The yield of semi-insulator substrates per pear-shaped crystal is improved.
[0434] Example 28
[0435] U.S. Patent Application Publication No. 6,824,611
[0436] The present embodiment discloses an apparatus and method for achieving controlled, extended and repeatable high quality silicon carbide growth with a preferred polytype, wherein the apparatus utilizes a graphite crucible having a coating, wherein the coating is a metal carbide, and preferably a thin carbide coating selected from the group consisting of tantalum carbide, hafnium carbide, niobium carbide, titanium carbide, zirconium carbide, tungsten carbide and vanadium carbide.
[0437] Silicon carbide is a long-standing candidate for semiconductor material applications. Silicon carbide has a wide bandgap and a low dielectric constant, and is stable at temperatures far higher than those that make other semiconductor materials (such as silicon) unstable. These characteristics give silicon carbide excellent semiconductor properties. Compared to devices produced from other conventional semiconductor materials (such as silicon), electronic devices made of silicon carbide can be particularly expected to operate at higher temperatures, speeds, and radiation densities.
[0438] As will be appreciated by those familiar with solid-state physics and semiconductor behavior, semiconductor materials must possess certain specific properties in order to be useful as materials for the preparation of electrical devices. Many applications require the use of single crystals with low levels of defects in the crystal lattice and low levels of undesirable chemical and physical impurities. Materials with uncontrolled impurities are unsatisfactory for electrical device applications. Even in pure materials, defects in the lattice structure can render them unusable.
[0439] In addition to its electrical properties, silicon carbide possesses other desirable physical properties. Silicon carbide is very hard, with a hardness of 8.5 to 9.25 Mohs, depending on its polytype (e.g., atomic arrangement) and crystal orientation. In comparison, diamond has a hardness of 10 Mohs. Silicon carbide is scintillation-resistant, with a refractive index of 2.5-2.71, depending on its polytype. In comparison, diamond has a refractive index of about 2.4. In addition, silicon carbide is a tough and stable material that can be heated to over 2,000°C in air without damage. These physical properties make silicon carbide an ideal replacement for naturally occurring gemstones. The use of silicon carbide as a gemstone is described in U.S. Patents Nos. 5,723,391 and 5,762,896 to Hunter et al.
[0440] Accordingly, since the physical properties and potential uses of silicon carbide have been recognized for some time, many researchers have proposed several techniques for preparing silicon carbide crystals. These techniques are roughly divided into two categories, although some techniques cannot be easily classified. The first category of techniques is called chemical vapor deposition (CVD), in which reactants and gases are introduced into a system and silicon carbide crystals are produced on a suitable substrate in the system.
[0441] Another large class of techniques for growing silicon carbide crystals is generally referred to as sublimation techniques. As the word "sublimation" suggests, sublimation techniques generally use some solid silicon carbide starting material that is heated until the silicon carbide sublimates. The vaporized silicon carbide starting material then condenses on a substrate, such as a seed crystal in the case of producing a desired crystal polymorph.
[0442] One of the earliest sublimation techniques with practical use for producing better crystals was developed by JA Lely in the 1950s and described in U.S. Patent No. 2,854,364. In general, Lely's technique lines the interior of a carbon container with a silicon carbide source material. The technique deposits recrystallized silicon carbide on the container lining by heating the container to a temperature at which silicon carbide sublimates and then condensing the sublimate.
[0443] The Lely sublimation technique has been improved by several researchers. Hergenrother's U.S. Patent No. 3,228,756 (hereinafter referred to as Hergenrother'756) discusses another sublimation growth technique that uses a silicon carbide seed crystal, and other silicon carbide condenses on the surface of the seed crystal to grow crystals. Hergenrother'756 proposed that in order to promote reasonable growth, the seed crystal must be heated to an appropriate temperature, usually above 2,000°C, and during the heating process, the residence time of the seed crystal at 1,800°C to 2,000°C is shortened to a minimum.
[0444] U.S. Patent No. 3,236,780 to Ozarow (hereinafter referred to as Ozarow '780) discusses another unseeded sublimation technique that uses a silicon carbide liner within a carbon container. Ozarow '780 attempts to establish a radial temperature gradient between an inner silicon carbide liner and an outer silicon carbide liner within the container.
[0445] Knippenberg's U.S. Pat. Nos. 3,615,930 (hereinafter Knippenberg'930) and 3,962,406 (hereinafter Knippenberg'406) discuss alternative methods of growing the desired silicon carbide crystal. Knippenberg'930 discusses growing pn junctions in silicon carbide crystals obtained by sublimation growth techniques. According to the discussion in the patent, silicon carbide is heated in an inert gas in a closed space, the inert gas containing a donor-type dopant atom. The doping material is then purged from the container and the container is reheated in the presence of an acceptor dopant. The purpose of the technique is to make adjacent crystal portions have opposite conductivity types and thereby produce a pn junction.
[0446] Knippenberg '406 discusses a three-step process for preparing silicon carbide having a silicon dioxide core encased therein, and surrounding the core is granular silicon carbide or material that will form silicon carbide. The silicon carbide and silicon dioxide encasing material are then heated. The system is heated to a temperature such that a silicon carbide shell forms around the silicon dioxide core, and the system is then further heated to sublime the silicon dioxide core within the silicon carbide shell. Finally, the system is further heated to promote the continued growth of additional silicon carbide within the silicon carbide shell.
[0447] US Patent No. 4,147,572 to Vodakov discusses a geometrically oriented sublimation technique in which a solid silicon carbide source material and a seed crystal are placed parallel to each other.
[0448] Addamiano's U.S. Pat. No. 4,556,436 (hereinafter Addamiano '436) discusses a Lely-type furnace apparatus for producing β-type silicon carbide thin films on α-type silicon carbide, characterized by rapid cooling from a sublimation temperature of 2,300° C. to 2,700° C. to a temperature below 1,800° C. Addamiano '436 points out that for this furnace apparatus, bulk single crystals of cubic (β-type) silicon carbide are unavailable, and the growth of silicon carbide or other materials such as silicon or diamond is very difficult.
[0449] Hsu, U.S. Pat. No. 4,664,944, discusses a fluidized bed technique for preparing silicon carbide single crystals that is similar to chemical vapor deposition techniques when using non-silicon carbide reactants, but contains silicon carbide particles in the fluidized bed, thus somewhat similar to sublimation techniques.
[0450] German (Federal Republic of) Patent No. 3,230,727 to Siemens Coproation discusses a silicon carbide sublimation technique, with a focus on minimizing the thermal gradient between the silicon carbide seed and the silicon carbide source material. The patent suggests limiting the thermal gradient to no more than 20°C per centimeter (the distance between the seed and the source material in the reaction vessel). The patent also suggests maintaining the vapor pressure in the sublimation system at 1 to 5 millibars, and preferably at 1.5 to 2.5 millibars.
[0451] Davis' U.S. Patent No. Re. 34,861 (hereinafter referred to as Davis'861) discusses a method for preparing a large device quality silicon carbide single crystal. The patent discloses a sublimation process that is enhanced by maintaining a constant polymorph composition and particle size distribution of the source material. The patent also discusses the specific preparation of the growth surface and the seed crystal, as well as the control of the thermal gradient between the source material and the seed crystal.
[0452] Barrett's U.S. Pat. No. 5,746,827 (hereinafter referred to as Barrett'827) discusses a method for preparing large diameter silicon carbide crystals that requires two growth stages. The first growth stage is to isothermally grow the seed crystal to a larger diameter. The second growth stage is to grow a large diameter pear-shaped crystal on the seed crystal under thermal gradient conditions.
[0453] Hopkins' U.S. Pat. No. 5,873,937 (hereinafter referred to as Hopkins '937) discusses a method of growing 4H silicon carbide crystals. The patent teaches a physical vapor transport (PVT) system in which the surface temperature of the crystal is maintained below about 2,160°C and the pressure within the PVT system is reduced to compensate for the lower growth temperature.
[0454] Kitoh's US Pat. No. 5,895,526 (hereinafter Kitoh '526) teaches a sublimation process for growing a silicon carbide single crystal, wherein a sublimated source material flows parallel to the surface of a single crystal substrate.
[0455] Although significant progress has been made in the production of SiC crystals over the years, there is still progress to be made in its significant commercial application. For example, faster and more powerful prototype devices are being developed, which require larger SiC crystals whose quality must maintain or exceed the crystal quality currently achievable. Pear-shaped crystals large enough to be used to prepare 50mm diameter SiC wafers are currently the limit of what can be achieved in commercially viable SiC production. The preparation of 75mm diameter SiC wafers with good quality is possible, but not yet commercially viable, and there is currently a demand for 100mm wafers. Many SiC crystal production technologies cannot economically and sustainably produce crystals of the required size and quality. The main reason for this is the chemical properties of SiC.
[0456] Known methods of growing silicon carbide crystals are difficult, if not impossible, to accomplish due to the chemical processes of silicon carbide sublimation and crystallization. The stoichiometry of the crystal growth process is extremely important and complex, and too much or too little silicon or carbon in the sublimation vapor can result in crystals with undesirable polymorphs and defects (e.g., micropipes).
[0457] Similarly, the higher operating temperatures (typically above 2,100°C) and the necessity to create a specific temperature gradient within the crystal growth system create significant operational difficulties. Conventional graphite sublimation vessels used by most sublimation systems have an infrared emissivity on the order of 0.85 to 0.95, depending on the surface characteristics of the vessel. The seed crystal is thermally sensitive to infrared radiation. Therefore, the infrared radiation emitted by the graphite vessel can excessively heat the seed crystal and thus complicate the precise temperature gradient necessary for successful operation of the sublimation system.
[0458] recent, The SiC research group at the University of Michigan demonstrated a SiC growth technique called High Temperature Chemical Vapor Deposition (HTCVD), which refers to the article "High Temperature Chemical Vapor Deposition" presented by O. Kordina et al. at the 1995 International Conference on SiC and Related Materials in Kyoto, Japan; and the article 69 Applied Physics Letters, 1456 (1996) by O. Kordina et al. In this technique, the solid silicon source material is replaced by a gas (such as silane). The use of a gaseous source material improves the control of the stoichiometry of the reaction. The solid carbon source material can also be replaced by a gas (such as silane); however, most of the carbon used in this technique actually comes from the graphite wall of the crucible. In theory, the use of a continuous gas supply in this technique will allow continuous and extended SiC pear-shaped crystal growth. Unfortunately, for pear-shaped crystal growth, this HTCVD technology has not yet been proven to be commercially viable, mainly because the reaction in this technology can destroy the graphite crucible. Furthermore, the hydrocarbon gas added by this technique tends to produce Si droplets laden with SiC, which reduces efficiency and changes the stoichiometry of the system by carrying Si and C.
[0459] The most difficult aspect of growing silicon carbide is the reactivity of silicon at high temperatures. Silicon reacts with the graphite container used in most sublimation processes, and as mentioned above, this reaction is promoted in certain applications. This reaction is difficult to control and often leaves too much silicon or carbon in the system, thus changing the stoichiometry of the crystal growth process. In addition, silicon's attack on the graphite container causes the walls of the container to dent and then break, and produces carbon dust that can contaminate the crystal.
[0460] In an attempt to address the above difficulties, some studies have evaluated the presence of tantalum in sublimation systems, such as Yu.A.Vodakov et al. at the Sixth International Conference on Silicon Carbide in Kyoto, Japan in September 1995 (6 thInternational Conference on Silicon Carbide, September 1995, Kyoto, Japan) presented "The Use of Tantalum Container Material for Quality Improvement of SiC Crystals Grown by the Sublimation Technique," an article. Some researchers believe that tantalum can help maintain the stoichiometry required for optimal crystal growth. This view is supported by some reports that sublimation containers containing tantalum are less susceptible to attack from reactive silicon.
[0461] In a related application, Vodakov's patent WO97 / 27350 (hereinafter referred to as Vodakov'350) discloses a sublimation technique that is similar to the technique disclosed in U.S. Patent No. 4,147,572 and attempts to address the problem of silicon attacking structural components of the sublimation system. Vodakov'350 describes a geometrically oriented sublimation technique in which a solid silicon carbide source material and a seed crystal are placed parallel to each other. Vodakov'350 uses a sublimation container made of solid tantalum. The inner surface of the Vodakov tantalum container is described as an alloy of tantalum, silicon and carbon. On page 11, line 26 to page 12, line 10 of Vodakov'350, Vodakov states that the container can resist attack by silicon vapor and help produce well-structured silicon carbide crystals.
[0462] However, the cost of tantalum is one of the drawbacks of the sublimation process described by Vodakov using tantalum containers. Sublimation containers made from solid tantalum are extremely expensive and, like all sublimation containers, will eventually fail, making the long-term use of tantalum containers very uneconomical. Solid tantalum sublimation containers are also difficult to manufacture mechanically. Producing the container physically is not an easy task. Finally, the sublimation process disclosed by Vodakov '350 suffers from the same deficiencies that occur with other solid source sublimation techniques, which prevent the process from being able to efficiently produce large, high quality pear-shaped crystals for new applications.
[0463] Therefore, there is a need for a process that can provide controlled, extended and repeatable high quality SiC crystal growth. The system in this process must provide a container that can withstand attack from silicon. The system should also be economical and usable.
[0464] Fig. 9The GFS system shown includes a widely placed crucible 910. It should be understood that the crucible 910 is essentially a closed structure, similar to the type of crucible commonly used in SiC sublimation technology. This embodiment refers to the crucible in Barrett'827, the growth chamber in Hopkins'937, and the crucible shown in the drawings of Davis'861, which are only exemplary and not limiting the crucible, chamber or container of this embodiment. These references also illustrate that the broad parameters in the sublimation growth technology are also relatively well known in the art. Accordingly, these references will not be discussed in more detail except for describing the features of this embodiment. Crucible 910 is generally cylindrical and includes a cylindrical wall 911, which has an outer surface 912 and an inner surface 913. The cylindrical wall is made of graphite and coated with a material with a melting point above the sublimation temperature of SiC. The coating material is also characterized by being chemically inert to silicon and hydrogen at an uncertain temperature. Metal carbides, and in particular carbides of tantalum, hafnium, niobium, titanium, zirconium, tungsten and vanadium and their various mixtures, exhibit the properties required of the coating. Metal nitrides, and in particular nitrides of tantalum, hafnium, niobium, titanium, zirconium, tungsten and vanadium and their various mixtures, also exhibit the properties required of the coating. In addition, mixtures of metal carbides and metal nitrides, such as those described above, may also be used as coatings. For ease of discussion and reference, the remainder outside of this specific description will refer to metal carbides, even though it should be understood that the concepts and principles discussed in this embodiment are equally applicable to metal nitride coatings.
[0465] In all cases described in this embodiment, it is understood that the graphite parts exposed to the source material are coated with a metal carbide coating. The metal carbide coating can be provided by any commercially viable coating process, such as the process used by Ultramet Corporation of Pacoima, Calif. or Advance Ceramics Corporation of Lakewood, Ohio. In addition, the graphite parts described in this embodiment are produced from graphite having the same thermal expansion coefficient as the selected metal carbide. The above materials are commercially available. Relatively similar thermal expansion coefficients are required for materials heated to the temperatures described in this embodiment. In this way, the possibility of cracking of the graphite and metal carbide coating in this process during crystal growth will be substantially reduced, and the life of the crucible will also be generally improved.
[0466] The cylindrical wall 911 radially encloses a reaction region 914. The outer 916 and inner coaxial source gas channels 918 supply source gas materials to the reaction region 914. Although the source gases may be mixed before entering the reaction region 914, separating the gas components of the source gases from each other before being heated to the reaction temperature helps to avoid undesirable side reactions between the silicon source gas and the carbon source gas. The coaxial channels maintain the separation of the source gas materials from each other before the source gases enter the reaction region 914. In a preferred embodiment, the outer coaxial source gas channel 916 supplies the carbon source gas to the reaction region 914, and the inner coaxial source gas channel 918 supplies the silicon source gas.
[0467] In a typical sublimation system, the graphite wall of the crucible is used as a source of carbon. Metal carbide coatings reduce the availability of this carbon source, although in certain specific cases, the coated graphite can still serve as a carbon source. Accordingly, most of the required carbon is supplied by an external source, such as a carbon source gas. Suitable carbon source gases include any hydrocarbon that can react with Si to produce SiC: C 2 To C 8 Hydrocarbons, and especially ethylene (C 2 H 4 The carbon source gas stream may also include one or more carrier gases, such as He or H 2 .
[0468] Suitable carbon source gases include any gas that can react with available carbon to produce SiC. Silane (SiH 4 ) is probably the most well-known suitable silicon source gas. Other suitable silicon source gases include chlorosilane (SiH 4 -xCl x ) and trichloromethylsilane (CH 3 SiCl 3 ). However, chlorosilanes require H 2 The silicon source gas flow may also include an inert carrier gas, such as He.
[0469] Seed crystal 922 is fixed on seed crystal holder 920 and lowered into reaction region 914. Source gases react in reaction region 914 to produce SiC vapor, which is ultimately deposited on the surface of seed crystal 922 to form pear-shaped crystal 924. It is believed that at least a portion of the SiC is first deposited on inner wall 913, then sublimates and condenses on the growth surface (seed crystal 922 or pear-shaped crystal 924). In most cases, the seed crystal is preferably SiC of the same polytype as the grown crystal.
[0470] The composition of the source gases may be held constant or varied during the growth process depending upon the desired stoichiometry, the type of crystal, and the physical characteristics of the crystal growth system.
[0471] It will be appreciated by those skilled in the physical chemistry of solids, liquids and gases that crystal growth is preferably carried out on a growth surface in most cases, provided that the temperature of the growth surface is lower than the temperature of the fluid (gas or liquid) carrying the molecules or atoms to be condensed. The GFS system is no exception. A thermal gradient is established between the growth surface and the source material. Although the specific magnitude of the thermal gradient may vary depending on the pressure in the system, the desired polytype, the source gas composition, etc., the following general principles apply to all types of SiC crystal growth processes, including the GFS system. The temperature of the silicon source and the carbon source should be raised to a temperature sufficient to form vapors, and the temperature of the crystal growth surface is raised to a temperature close to the temperature of the silicon source and the carbon source, but lower than that temperature, and also lower than the temperature at which the sublimation rate of SiC in the gas pressure used is higher than the deposition rate.
[0472] As mentioned above, many variables determine the appropriate temperature gradient required for a system. However, it has been found that Figure 1 The system shown works well when the seed temperature is between about 1,900°C and about 2,500°C, while the inner wall temperature of the reaction zone is about 150°C to about 200°C higher than the seed temperature. The maximum growth rate of such a system has yet to be determined. Higher temperatures are known to translate into faster growth rates. However, higher temperatures can cause the seed to sublime, which changes the balance of the system and requires additional source gases and other adjustments.
[0473] Figure 1 The GFS system shown demonstrates the ability to produce very large, high-quality SiC crystals. More importantly, Figure 1 The GFS system shown demonstrates the ability to withstand attack from Si compounds, which can ultimately destroy a graphite crucible. In testing, a graphite crucible coated with a 30 micron thick TaC coating that emerged during crystal growth was unaffected by the harsh environment. Cracks appeared in the test crucible after only a few cycles, often near sharp corners where metal carbide coatings are less well-coated. However, even though cracks in the coating occurred, the crystal growth system was not affected by carbon dust, which is typically generated when the integrity of a graphite crucible is compromised.
[0474] The explanation for this surprising property is not yet fully understood. Although the inventors do not wish to be bound by any particular theory, one possible explanation is that when uncoated graphite is attacked by Si, Si first attacks the weak parts of the graphite, such as penetrating from the particle boundaries into the pores. The Si is converted to SiC, which sublimates and is removed as a volatile. Eventually, the Si completely corrodes the graphite near the particles, and the remaining particles become carbon dust particles. It is believed that the metal carbide coating penetrates deep into the graphite pores, allowing Si to attack the graphite in a more uniform form, thereby avoiding the generation of carbon dust.
[0475] Surprisingly, a graphite crucible previously coated with a metal carbide coating can resist the formation of carbon dust even after substantial loss of the metal carbide coating has occurred. Accordingly, in an alternative embodiment, a GFS system includes a graphite crucible that was once coated with a metal carbide coating, but the crucible has lost some or all of its metal carbide coating due to use or other circumstances. Such a system is capable of producing high-quality SiC crystals without carbon dust contamination.
[0476] also, Figure 1 The illustrated GFS system also demonstrates the ability to provide better control of the temperature gradient within the growth system. As previously described, the seed is sensitive to infrared radiation, and the graphite has an infrared emissivity of about 0.85 to about 0.95 on its surface. In contrast, the infrared emissivity of the metal compound coating of the present embodiment is only about 0.4 for ZrC, about 0.5 for TaC, and about 0.6 for NbC. The lower infrared emissivity of the metal compound coating of the present embodiment substantially reduces the infrared exposure to the seed during crystal growth, and can reduce the temperature of the seed by 100°C or more compared to an uncoated graphite system. The reduction in infrared radiation can remove a potential source of excess heat from the system, thereby improving control of the temperature gradient within the system.
[0477] It is easy for a person skilled in the art to realize that the metal carbide coated crucible as described above can be easily applied to existing SiC crystal growth systems. It is also obvious to a person skilled in the art that the use of the metal carbide coated crucible according to the present embodiment need not be limited to SiC sublimation growth. Therefore, although the present embodiment provides special advantages in SiC growth, coating and coated crucible, the chamber or container described in the present embodiment can provide structural and functional advantages for the growth of other materials, including other wide bandgap semiconductor materials, such as group III nitrides, and especially including gallium nitride (GaN). For example, some researchers have reported the association between carbon and yellow fluorescence in GaN, as well as the non-uniform electrical behavior in indium-containing nitrides (Pearton et al, GaN:Processing, Defects and Devices, 86 Applied Physics Reviews, 1 (July 1999)). The use of the device with coating and the method of the present embodiment advantageously reduces the availability of carbon as a potential residual impurity in MOCVD nitrides.
[0478] Fig.10 A cross-sectional view of another GFS system used in the method of this embodiment is shown. Therein, a crucible is generally located at 1010. The crucible 1010 is placed in a furnace generally located at 108. Methods and apparatus (e.g., furnaces) for supplying heat to SiC and other crystal growth systems are well known to those skilled in the art and therefore will not be discussed in detail in this embodiment.
[0479] The crucible 1010 is generally cylindrical and includes a cover 1026 and a bottom 1028 that enclose a cylindrical middle portion 1030. The cylindrical middle portion 1030 includes an outer cylinder 1032 having a top and a bottom, an inner diameter and an outer diameter. An inner cylinder 1034 is placed inside the inner diameter of the outer cylinder 1032, and the inner cylinder 1034 also has a top and a bottom, and an inner diameter and an outer diameter. The outer cylinder 1032 and the inner cylinder 1034 form a coaxial gas channel of the inner side 1038 and the outer side 1036.
[0480] In a preferred embodiment, the cylindrical middle part 1030 also includes at least one spacer ring 1040 between the outer cylinder 1032 and the cover 1026. The spacer ring 1040 is defined by an inner diameter and an outer diameter, and its inner diameter is smaller than the outer diameter of the inner cylinder 1034. The spacer ring 1040 and the cover 1026 generally define a reaction area 1042 above the outer 1032 and inner 1034 cylinders, respectively. It should be understood that the spacer ring 1040 is an optional component. However, when used, the spacer ring is preferably provided with the refractory metal carbide coating of this embodiment. Optionally, the outer cylinder 1032 can be extended to replace the spacer ring 1040. However, this embodiment still recommends the use of a single or multiple spacer rings, because it can provide flexibility in adjusting the size of the reaction area 1042 and the thermal gradient. In a further alternative embodiment, the spacer ring 1040 can be used in conjunction with other similarly shaped devices, such as a growth plate (a ring with a venturi-like opening that focuses the upward-flowing SiC vapor) or a collection plate (a porous plate that collects solid particles that fall off the crucible wall while allowing the SiC vapor to flow upward). Collecting these particles on a hot collection plate allows them to re-sublime and assist in crystal growth.
[0481] The seed crystal 1044 extends from the cover 1026 into the reaction region 1042 and is fixed by a seed crystal holder 1046 and a graphite rod 1048. The seed crystal 1044 serves as a substrate for the growth of SiC pear-shaped crystals 1050.
[0482] The two gas sources 1052 and 1054 are in fluid communication with the inner and outer coaxial gas channels and provide silicon and carbon source gases for the SiC crystal growth process. In a preferred embodiment, one gas source 1052 supplies carbon source gas to the outer coaxial gas channel 1036, and the other gas source 1054 supplies silicon source gas to the inner coaxial gas channel 1038. The reaction of generating SiC vapor and the desired SiC pear-shaped crystal is as previously described (according to Fig. 9 A gas inlet 1027 is incorporated into the lid 1026 and extends through the bottom of the seed holder 1046, the gas inlet 1027 providing a means for gas to be purged from the reaction zone 1042.
[0483] It is further understood that relevant portions of previously referenced systems (eg, Davids, Vodakov, etc.) may be modified and improved to incorporate the coated surfaces, chambers, and systems described in the present embodiment and fall within the coefficients of the present embodiment.
[0484] Example 29
[0485] This example uses 6-nines, and preferably 7-nines pure (higher purity may also be used) polysilicon carbide derived SiC or SiOC disclosed and taught in patent applications serial numbers 14 / 864,539 (U.S. Publication No. 2016 / 0208412), 14 / 864,125 (U.S. Publication No. 2016 / 0207782) and PCT / US2015 / 051997 (Publication No. WO 2016 / 049344), for example as seeds, starting crystals, growth materials, source materials, deposition materials and raw materials in the apparatus and processes disclosed and taught in U.S. Patent No. 7,501,022, all disclosures of which are incorporated herein by reference.
[0486] Example 30
[0487] This example uses 6-nines, and preferably 7-nines pure (higher purity may also be used) polysilicon carbide derived SiC or SiOC disclosed and taught in patent applications serial numbers 14 / 864,539 (U.S. Publication No. 2016 / 0208412), 14 / 864,125 (U.S. Publication No. 2016 / 0207782) and PCT / US2015 / 051997 (Publication No. WO 2016 / 049344), for example as seeds, starting crystals, growth materials, source materials, deposition materials and raw materials in the apparatus and processes disclosed and taught in U.S. Patent No. 8,377,806, all disclosures of which are incorporated herein by reference.
[0488] Example 31
[0489] This example uses 6-nines, and preferably 7-nines pure (higher purity may also be used) polysilicon carbide derived SiC or SiOC disclosed and taught in patent applications with serial numbers 14 / 864,539 (U.S. Publication No. 2016 / 0208412), 14 / 864,125 (U.S. Publication No. 2016 / 0207782) and PCT / US2015 / 051997 (Publication No. WO 2016 / 049344), for example as seeds, starting crystals, growth materials, source materials, deposition materials and raw materials in the apparatus and processes disclosed and taught in U.S. Patent No. 6,706,114, all disclosures of which are incorporated herein by reference.
[0490] Example 32
[0491] This example uses 6-nines, and preferably 7-nines pure (higher purity may also be used) polysilicon carbide derived SiC or SiOC disclosed and taught in patent applications with serial numbers 14 / 864,539 (U.S. Publication No. 2016 / 0208412), 14 / 864,125 (U.S. Publication No. 2016 / 0207782) and PCT / US2015 / 051997 (Publication No. WO 2016 / 049344), for example as seeds, starting crystals, growth materials, source materials, deposition materials and raw materials in the apparatus and processes disclosed and taught in U.S. Patent No. 8,492,827, all disclosures of which are incorporated herein by reference.
[0492] Example 33
[0493] This example uses 6-nines, and preferably 7-nines pure (higher purity may also be used) polysilicon carbide derived SiC or SiOC disclosed and taught in patent applications with serial numbers 14 / 864,539 (U.S. Publication No. 2016 / 0208412), 14 / 864,125 (U.S. Publication No. 2016 / 0207782) and PCT / US2015 / 051997 (Publication No. WO 2016 / 049344), for example as seeds, starting crystals, growth materials, source materials, deposition materials and raw materials in the apparatus and processes disclosed and taught in U.S. Patent No. 8,329,133, all disclosures of which are incorporated herein by reference.
[0494] Example 34
[0495] This example uses 6-nines, and preferably 7-nines pure (higher purity may also be used) polysilicon carbide derived SiC or SiOC disclosed and taught in patent applications serial numbers 14 / 864,539 (U.S. Publication No. 2016 / 0208412), 14 / 864,125 (U.S. Publication No. 2016 / 0207782) and PCT / US2015 / 051997 (Publication No. WO 2016 / 049344), for example as seeds, starting crystals, growth materials, source materials, deposition materials and raw materials in the apparatus and processes disclosed and taught in U.S. Patent No. 6,0191,841, all disclosures of which are incorporated herein by reference.
[0496] It should be noted that the present invention does not require a theoretical explanation for its innovative and breakthrough processes, materials, performances, or other beneficial characteristics and properties associated with the embodiments of the present invention or its subject matter. Nevertheless, a variety of different theories are provided in the present invention specification to advance the art. These theories disclosed in the present invention specification, unless otherwise stated, in no way limit, restrict or narrow the scope of protection of the present invention. These theories may not be needed or used in the present invention. It should be further understood that the present invention can lead to new, previously unknown theories to explain the functional characteristics of the embodiments of the methods, products, materials, devices and systems of the present invention; such later developed theories do not limit the scope of protection of the present invention.
[0497] The various different formulations, batches, materials, composites, devices, systems, apparatuses, operating activities and method embodiments disclosed in the present specification can be used in fields where SiC and Si are applied, as well as fields where SiC or / and Si cannot be applied in a feasible manner (cost or / and performance). In addition, the various different embodiments disclosed in the present specification can be applied in various different combinations with each other. Thus, for example, the configurations provided by the various different embodiments in the present description can be applied in combination with each other; and the scope of protection of the present invention is not limited to a particular embodiment, configuration or a particular embodiment, example or arrangement disclosed in the embodiment of the accompanying drawings.
[0498] The present invention may be embodied in other forms than those disclosed in this application without departing from its teachings or essential characteristics. The above described embodiments should be regarded as an explanation of the present invention rather than a limitation on the protection scope of the present invention.
Claims
1. A method of preparing a pear-shaped crystal for producing a 6- to 10-inch diameter 4H N-type silicon carbide wafer characterized by the following properties: Type / dopant: N / nitrogen; Crystal orientation: <0001> 4.0°±0.5°; Thickness: 300 μm to 800 μm; and Microtubule density <1cm -2 ; and, The method comprises the following steps: forming a vapor of a polymer derived ceramic SiC starting material, wherein the polymer derived ceramic SiC starting material has a purity of at least 6 nines and is free of an oxide layer; depositing the vapor onto a seed crystal to form a pear-shaped crystal; and providing the pear-shaped crystal to a wafer preparation process, The polymer derived ceramic SiC starting material is polysilicon oxycarbide derived SiC and is made by solidification and pyrolysis of SiOC material, and the polymer derived ceramic SiC starting material includes a SiC4 structural configuration and has a volume shape.
2. The method according to claim 1, wherein the characteristics of the wafer further include a resistivity of 0.02-0.2 Ω·cm.
3. The method according to claim 1, wherein the characteristics of the wafer further include a resistivity of 0.01-0.1 Ω·cm.
4. The method according to claim 1, wherein the characteristics of the wafer further include a resistivity of 0.1-40 Ω·cm.
5. The method of claim 1, 2, 3 or 4, wherein the seed comprises a polymer derived ceramic SiC.
6. The method of claim 1, wherein the wafer preparation process produces a wafer having improved characteristics compared to wafers made from non-polymer derived SiC materials.
7. The method of claim 2, wherein the wafer preparation process produces a wafer having improved characteristics compared to wafers made from non-polymer derived SiC materials.
8. The method of claim 3, wherein the wafer preparation process produces a wafer having improved characteristics compared to wafers made from non-polymer derived SiC materials.
9. The method of claim 4, wherein the wafer preparation process produces a wafer having improved characteristics compared to wafers made from non-polymer derived SiC materials.
10. The method of claim 6, 7, 8 or 9, wherein the modified feature is selected from the group consisting of curvature, edge profile, flatness, focal plane, warp, and local flatness.
11. A method for preparing a 4H silicon carbide wafer, the method comprising the following steps: forming a vapor of a polymer derived ceramic SiC having a purity of at least 6 nines and being free of an oxide layer, depositing the vapor onto the seed crystal to form a pear-shaped crystal, and providing the pear-shaped crystal to a wafer preparation process, wherein the pear-shaped crystal has a diameter of 6 inches to 10 inches, The polymer derived ceramic SiC starting material is polysilicon oxycarbide derived SiC and is made by solidification and pyrolysis of SiOC material, and the polymer derived ceramic SiC starting material includes a SiC4 structural configuration and has a volume shape.
12. The method of claim 11, wherein the seed crystal comprises polymer derived ceramic 4H SiC.
13. The method of claim 11, wherein the wafer preparation process produces a wafer having improved characteristics selected from the group consisting of bow, edge profile, flatness, focal plane, warp, and local flatness compared to wafers made from non-polymer derived SiC materials.
14. A method of preparing a pear-shaped crystal for producing a 4H N-type silicon carbide wafer having a diameter of 4 to 10 inches, said wafer being characterized by the following properties: Type / dopant: N / nitrogen; Crystal orientation: <0001> 4.0°±0.5°; Thickness: 300 μm to 800 μm; and Microtubule density <1cm -2 ;and, Resistivity: 0.01-40Ω·cm; and, Curvature / warpage / TTV<45μm; The method comprises the following steps: forming a vapor of a polymer derived ceramic SiC starting material; wherein the polymer derived ceramic SiC starting material has a purity of at least 6 nines; depositing the vapor onto a seed crystal to form a pear-shaped crystal; and providing the pear-shaped crystal to a wafer preparation process, The polymer derived ceramic SiC starting material is polysilicon oxycarbide derived SiC and is made by solidification and pyrolysis of SiOC material, and the polymer derived ceramic SiC starting material includes a SiC4 structural configuration and has a volume shape.
15. The method of claim 14, wherein the seed crystal is a polymer derived ceramic SiC.
16. The method according to claim 14, wherein the resistivity is 0.1-40 Ω·cm.
17. The method according to claim 14, wherein the resistivity is 0.02-0.2 Ω·cm.
18. The method of claim 14, 15, 16 or 17, wherein the bow / warp / TTV < 35 μm.
19. The method of claim 14, 15, 16 or 17, wherein the bow / warp / TTV < 25 μm.
20. A method of preparing a pear-shaped crystal for producing a 4H N-type silicon carbide wafer having a diameter of 8 to 12 inches, said wafer being characterized by the following properties: Type / dopant: N / nitrogen; Crystal orientation: <0001> 4.0°±0.5°; Thickness: 300 μm to 800 μm; and Microtubule density <1cm -2 ; and, The method comprises the following steps: forming a vapor of a polymer derived ceramic SiC starting material, wherein the polymer derived ceramic SiC starting material has a purity of at least 6 nines and is free of an oxide layer; depositing the vapor onto a seed crystal to form a pear-shaped crystal; and providing the pear-shaped crystal to a wafer preparation process, The polymer derived ceramic SiC starting material is polysilicon oxycarbide derived SiC and is made by solidification and pyrolysis of SiOC material, and the polymer derived ceramic SiC starting material includes a SiC4 structural configuration and has a volume shape.
21. A method for preparing a 4H silicon carbide wafer, the method comprising the following steps: forming a vapor of a polymer derived ceramic SiC having a purity of at least 6 nines and being free of an oxide layer, depositing the vapor onto the seed crystal to form a pear-shaped crystal, and providing the pear-shaped crystal to a wafer preparation process, wherein the diameter of the pear-shaped crystal is 8 inches to 12 inches, The polymer derived ceramic SiC starting material is polysilicon oxycarbide derived SiC and is made by solidification and pyrolysis of SiOC material, and the polymer derived ceramic SiC starting material includes a SiC4 structural configuration and has a volume shape.
22. A method of preparing a pear-shaped crystal for producing a 4H N-type silicon carbide wafer having a diameter of 8 to 12 inches, said wafer being characterized by the following properties: Type / dopant: N / nitrogen; Crystal orientation: <0001> 4.0°±0.5°; Thickness: 300 μm to 800 μm; and Microtubule density <1cm -2 ;and, Resistivity: 0.01-40Ω·cm; and, Curvature / warpage / TTV<45μm; The method comprises the following steps: forming a vapor of a polymer derived ceramic SiC starting material; wherein the polymer derived ceramic SiC starting material has a purity of at least 6 nines; depositing the vapor onto a seed crystal to form a pear-shaped crystal; and providing the pear-shaped crystal to a wafer preparation process, The polymer derived ceramic SiC starting material is polysilicon oxycarbide derived SiC and is made by solidification and pyrolysis of SiOC material, and the polymer derived ceramic SiC starting material includes a SiC4 structural configuration and has a volume shape.
Citation Information
Patent Citations
Method for manufacturing silicon carbide single crystal
US20130255568A1
Polysilocarb based silicon carbide materials, applications and devices
US20160207782A1
HIGH PURITY SiOC AND SiC, METHODS COMPOSITIONS AND APPLICATIONS
US20160208412A1
Sublimation process for manufacturing silicon carbide crystals
US2854364A
Method of growing single crystal silicon carbide
US3228756A